Composite garnet electrolyte with porous surface, battery and manufacturing method thereof
By providing excess lithium in the composite garnet electrolyte and forming a porous surface, the capacity maintenance and life problems of Li metal batteries during high capacity operation are solved, achieving higher battery performance and stability.
Patent Information
- Application Number
- CN202311426590.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
Conventional Li metal batteries are prone to capacity maintenance and life problems when running at high capacity.
By providing excess lithium in the composite garnet electrolyte, mixed intergranular and transgranular microstructures are formed, and electrolytes with porous surfaces are formed by acid etching.
Low interface resistance, increased charging performance and cycle stability are achieved, and the battery ring strength is improved.
Smart Images

Figure CN119920958A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a composite porous garnet electrolyte, a battery and a method for manufacturing the same, and more particularly, to a battery including a composite garnet electrolyte having a porous surface and a method for manufacturing the same. Background Art
[0002] Solid-state batteries (SSBs), such as SS lithium (Li) metal batteries based on inorganic solid electrolytes (SSEs) such as garnet-type SSEs, have attracted extensive attention due to their high safety, improved energy density, high ionic conductivity, and stability compared to Li metal. However, conventional Li metal batteries often suffer from capacity retention and / or lifespan issues, especially when operating at higher capacities. Therefore, there is a need to address these issues. Summary of the invention
[0003] The present disclosure provides solid electrolytes, batteries and methods for making the same, wherein the surface (or surfaces) of the solid electrolytes included can be easily etched to form an electrolyte having a porous surface (e.g., a composite garnet electrolyte having a porous surface). An electrolyte having a porous surface (e.g., a composite garnet electrolyte having a porous surface) can achieve lower interface resistance, increased charging performance and / or increased cycle stability. In addition, an electrolyte having a porous surface (e.g., a composite garnet electrolyte having a porous surface) can achieve high ring-on-ring strength (e.g., about 150 MPa or more or about 150 MPa to about 600 MPa).
[0004] As described herein, providing an excess of lithium in the composite garnet electrolyte (e.g., 0.1 wt % to 4 wt %, 0.2 wt % to 1.1 wt %, or 0.3 wt % to 0.9 wt % more relative to the stoichiometric ratio) can help form a mixture of intergranular and transgranular microstructures and help etch the solid electrolyte (e.g., composite garnet electrolyte) to form a solid electrolyte with a porous surface (e.g., a composite garnet electrolyte with a porous surface). For example, providing 11.2 wt % to 15 wt % or 11.3 wt % to 12.2 wt % can form an intergranular microstructure near the major surface of the composite garnet electrolyte, which can help etch the composite garnet electrolyte to form a porous surface of the solid electrolyte. Providing a transgranular microstructure near and / or at the first major surface can help form large and / or deep pores therein.
[0005] As described herein, the amount of lithium is determined based on flame emission spectroscopy, which means that the amount of lithium refers to the actual amount of lithium in the resulting solid electrolyte (e.g., composite garnet electrolyte). This is different from the amount of lithium that can be added to the garnet crystals before firing (e.g., sintering) to form the solid electrolyte, because it is known that lithium volatilizes during the firing process. As described in the examples below, adjusting the firing conditions themselves will change the amount of lithium present in the resulting solid electrolyte.
[0006] The green strip may contain excess lithium (e.g., 0.5 wt % or more, 2 wt % or more, or 10 wt % or more, based on the amount of garnet in the green strip) that is not completely removed by firing (e.g., sintering). The combination of firing conditions and excess lithium determines the amount of lithium that remains in the resulting electrolyte. If the firing temperature is too high (e.g., greater than 1200° C.) and / or the duration is too long (e.g., about greater than 60 minutes, depending on the temperature), the vast majority of the excess lithium added to the green strip may volatilize to produce an electrolyte that does not have a transgranular microstructure unlike aspects of the present disclosure.
[0007] Without wishing to be bound by theory, it is believed that the lithium phase between the garnet grains of the composite garnet electrolyte in the region having the intergranular microstructure may be preferentially etched, and thus the composite garnet electrolyte of the present disclosure may be more easily and / or more rapidly etched than other garnet electrolytes (e.g., with a stoichiometric amount of lithium). Providing a grain size of about 3 μm or less, about 1 μm to about 3 μm, or about 1 μm to about 2 μm may enable the ability to increase ionic conductivity, for example, by reducing the path length along the grain boundary (the ions transported through the solid electrolyte sheet will move along it) and / or by providing additional grain boundaries per unit volume of solid electrolyte. Providing deep pores (e.g., about 2 μm or greater, about 20 μm to about 60 μm, about 5% of the electrolyte thickness or greater, or about 10% to about 20% of the electrolyte thickness) may increase the effective surface area of the solid electrolyte (e.g., facing the anode and / or facing the cathode), which may reduce the interfacial resistance of a battery comprising a solid electrolyte (e.g., a composite garnet electrolyte having a porous surface).
[0008] Some exemplary aspects of the present disclosure are described below, and it is to be understood that any features of the various aspects may be used alone or in combination with each other.
[0009] Aspect 1: A method for manufacturing a porous surface of a composite garnet electrolyte, comprising:
[0010] etching at least a first major surface of the composite garnet electrolyte with an acid to form a porous surface of the garnet electrolyte comprising pores,
[0011] The composite garnet electrolyte comprises: an intergranular microstructure extending from a first major surface to a first depth, the composite garnet electrolyte comprising a lithium phase between garnet crystals, and an electrolyte thickness defined between the first major surface and a second major surface opposite to the first major surface.
[0012] Aspect 2: The method of aspect 1, wherein etching removes at least a portion of the lithium phase.
[0013] Aspect 3: The method of any of Aspects 1-2, wherein the amount of lithium in the composite garnet electrolyte is from about 11.2 wt % to about 15 wt % based on the oxide of the garnet electrolyte.
[0014] Aspect 4: The method of aspect 3, wherein the amount of lithium in the composite garnet electrolyte is about 11.3 wt % to about 12.2 wt %.
[0015] Aspect 5: The method of any of Aspects 3-4, wherein the amount of lithium in the composite garnet electrolyte is from about 11.4 wt % to about 12 wt %.
[0016] Aspect 6: The method of any of Aspects 1-2, wherein the amount of lithium in the composite garnet electrolyte is about 0.1 wt % to about 4 wt % greater than the stoichiometric lithium amount of the garnet crystals, based on the oxide of the composite garnet electrolyte.
[0017] Aspect 7: The method of aspect 6, wherein the amount of lithium in the composite garnet electrolyte exceeds the stoichiometric amount of lithium by about 0.2 wt % to about 1.1 wt %.
[0018] Aspect 8: The method of any of Aspects 6-7, wherein the amount of lithium in the composite garnet electrolyte exceeds the stoichiometric amount of lithium by about 0.3 wt % to about 0.9 wt %.
[0019] Aspect 9: The method of any of Aspects 1-8, wherein the intergranular microstructure extends from the first major surface to a first depth that is about 10% or more of the thickness of the electrolyte.
[0020] Aspect 10: The method of Aspect 9, wherein the composite garnet electrolyte comprises a transgranular microstructure located between regions comprising an intergranular microstructure.
[0021] Aspect 11: The method of any of Aspects 1-10, wherein the median grain size of the garnet crystals is less than 3 μm.
[0022] Aspect 12: The method of Aspect 11, wherein the median grain size of the garnet crystals is from about 1 μm to about 2 μm.
[0023] Aspect 13: The method of any of Aspects 1-12, wherein the mean pore diameter of the pores is greater than 0.25 μm.
[0024] Aspect 14: The method of aspect 13, wherein the mean pore size of the pores is 3 μm to about 20 μm.
[0025] Aspect 15: The method of any of Aspects 1-14, wherein the average pore depth of the pores is about 2 μm or greater.
[0026] Aspect 16: The method of any one of Aspects 1-15, further comprising:
[0027] Prior to etching, contacting the first major surface with water for at least 1 minute,
[0028] The acid concentration during the etching process is about 0.5M to about 5M.
[0029] Aspect 17: The method of Aspect 16, wherein etching is performed for a period of time of 3 minutes to 20 minutes.
[0030] Aspect 18: The method of any one of Aspects 1-17, further comprising:
[0031] casting a green ribbon comprising garnet, excess lithium, a binder, and a solvent, wherein the amount of excess lithium is greater than 0.5 wt % based on the weight % of the amount of garnet; and
[0032] The green strips are fired to form the composite garnet electrolyte.
[0033] Aspect 19: The method of Aspect 18, wherein the amount of excess lithium is from about 5 wt % to about 50 wt %, based on the weight % of the amount of garnet.
[0034] Aspect 20: The method of any of Aspects 18-19, wherein firing comprises heating the green strip at a temperature of about 900° C. to about 1200° C. for a period of 60 minutes or less.
[0035] Aspect 21: The method of Aspect 20, wherein the temperature is from about 1000°C to about 1125°C.
[0036] Aspect 22: The method of Aspect 20, wherein the time period is 5 minutes to 30 minutes.
[0037] Aspect 23: The method of any of Aspects 1-22, wherein the composite garnet electrolyte having a porous surface comprises a ring-on-ring strength of about 150 MPa to about 600 MPa.
[0038] Aspect 24: The method of any one of Aspects 1-23, wherein the garnet electrolyte having a porous surface has an interfacial resistance of less than or equal to 20Ω at 25°C.
[0039] Aspect 25: The method of any one of Aspects 1-24, wherein the battery containing the composite garnet electrolyte having a porous surface can withstand 2 mA / cm at 60°C. 2 or higher critical current density.
[0040] Aspect 26: The method of aspect 25, wherein the critical current density is 5 mA / cm 2 or higher.
[0041] Aspect 27: The method of any one of Aspects 1-26, wherein the battery containing the composite garnet electrolyte having a porous surface can withstand 70 cycles of 2 mA / cm 2 of charge and discharge cycles.
[0042] Aspect 28: The method of any of Aspects 1-27, wherein the garnet crystal is doped with tantalum.
[0043] Aspect 29: A composite garnet electrolyte comprising:
[0044] a hole extending from the first major surface; and
[0045] an intergranular microstructure extending from the first major surface to a first depth,
[0046] The intergranular microstructure includes: a lithium phase between garnet crystals, and an electrolyte thickness defined between a first major surface and a second major surface opposite to the first major surface.
[0047] Aspect 30: The composite garnet electrolyte of Aspect 29, wherein the amount of lithium in the composite garnet electrolyte is from about 11.2 wt % to about 15 wt % based on the oxide of the composite garnet electrolyte.
[0048] Aspect 31: The garnet electrolyte of Aspect 30, wherein the amount of lithium in the composite garnet electrolyte is from about 11.3 wt % to about 12.2 wt %.
[0049] Aspect 32: The garnet electrolyte of any of Aspects 30-31, wherein the amount of lithium in the composite garnet electrolyte is from about 11.4 wt % to about 12 wt %.
[0050] Aspect 33: The composite garnet electrolyte of Aspect 29, wherein the amount of lithium in the composite garnet electrolyte is about 0.1 wt % to about 4 wt % greater than the stoichiometric lithium amount of the garnet crystals, based on the oxide of the composite garnet electrolyte.
[0051] Aspect 34: The composite garnet electrolyte of Aspect 33, wherein the amount of lithium in the composite garnet electrolyte exceeds the stoichiometric amount of lithium by about 0.2 wt % to about 1.1 wt %.
[0052] Aspect 35: The composite garnet electrolyte of any of Aspects 33-34, wherein the amount of lithium in the composite garnet electrolyte exceeds the stoichiometric amount of lithium by about 0.3 wt % to about 0.9 wt %.
[0053] Aspect 36: The composite garnet electrolyte of any of Aspects 29-35, wherein the intergranular microstructure extends from the first major surface to a first depth of about 10% or more of the thickness of the electrolyte.
[0054] Aspect 37: The composite garnet electrolyte of Aspect 36, wherein the composite garnet electrolyte comprises a transgranular microstructure located between regions comprising an intergranular microstructure.
[0055] Aspect 38: The composite garnet electrolyte of any one of Aspects 29-37, wherein the median grain size of the garnet crystals is less than 3 μm.
[0056] Aspect 39: The composite garnet electrolyte of Aspect 38, wherein the median grain size of the garnet crystals is from about 1 μm to about 2 μm.
[0057] Aspect 40: The composite garnet electrolyte of any one of Aspects 29-39, wherein the mean pore size of the pores is greater than 1 μm.
[0058] Aspect 41: The composite garnet electrolyte of Aspect 40, wherein the mean pore size of the pores is 3 μm to about 20 μm.
[0059] Aspect 42: The composite garnet electrolyte of any of Aspects 29-41, wherein the average pore depth of the pores is about 2 μm or greater.
[0060] Aspect 43: The composite garnet electrolyte of any one of Aspects 29-42, wherein the electrolyte thickness is 20 μm to 200 μm.
[0061] Aspect 44: The composite garnet electrolyte of any of Aspects 29-43, wherein the garnet electrolyte comprises a ring-on-ring strength of about 150 MPa to about 600 MPa.
[0062] Aspect 45: The composite garnet electrolyte of any one of Aspects 26-44, wherein the garnet crystals are doped with tantalum.
[0063] Aspect 46: The composite garnet electrolyte according to any one of Aspects 29 to 45, wherein the interface resistance of the composite garnet electrolyte at 25° C. is less than or equal to 20Ω.
[0064] Aspect 47: A battery comprising:
[0065] A lithium-containing anode;
[0066] The composite garnet electrolyte of any one of aspects 29-46; and
[0067] cathode,
[0068] The garnet electrolyte is located between the lithium-containing anode and the cathode.
[0069] Aspect 48: The battery of Aspect 47, further comprising a lithium salt solution disposed between the composite garnet electrolyte and the cathode.
[0070] Aspect 49: The battery according to any one of Aspects 47-48, wherein the interface resistance of the battery at 25° C. is less than or equal to 20Ω.
[0071] Aspect 50: The battery of any one of Aspects 47-49, wherein the battery can withstand 2 mA / cm at 60°C. 2 or higher critical current density.
[0072] Aspect 51: The battery of Aspect 50, wherein the critical current density is 5 mA / cm 2 or higher.
[0073] Aspect 52: The battery of any one of Aspects 47-51, wherein the battery can withstand 70 cycles of 2 mA / cm 2 of charge and discharge cycles.
[0074] Aspect 53: A composite garnet electrolyte comprising:
[0075] an intergranular microstructure extending from the first major surface to a first depth,
[0076] The intergranular microstructure includes a lithium phase between garnet crystals, wherein the amount of lithium in the garnet electrolyte is about 0.1 wt % to about 4 wt % greater than the stoichiometric lithium amount of the garnet crystals, based on the oxide of the garnet electrolyte.
[0077] Aspect 54: The composite garnet electrolyte of Aspect 53, wherein the amount of lithium in the composite garnet electrolyte exceeds the stoichiometric amount of lithium by about 0.2 wt % to about 1.1 wt %.
[0078] Aspect 55: A composite garnet electrolyte comprising:
[0079] an intergranular microstructure extending from the first major surface to a first depth,
[0080] The intergranular microstructure includes a lithium phase between garnet crystals, and the amount of lithium in the composite garnet electrolyte is 11.3 wt % to 12.2 wt % based on the oxide of the composite garnet electrolyte.
[0081] Aspect 56: The composite garnet electrolyte of any of Aspects 53-55, wherein the amount of lithium in the porous garnet electrolyte is from about 11.4 wt % to about 12 wt %.
[0082] Aspect 57: The composite garnet electrolyte of any of Aspects 53-56, wherein the intergranular microstructure extends from the first major surface to a first depth of about 10% or more of the thickness of the electrolyte.
[0083] Aspect 58: The composite garnet electrolyte of Aspect 57, wherein the composite garnet electrolyte comprises a transgranular microstructure located between regions comprising an intergranular microstructure.
[0084] Aspect 59: The composite garnet electrolyte of any one of Aspects 53-58, wherein the median grain size of the garnet crystals is less than 3 μm.
[0085] Aspect 60: The composite garnet electrolyte of Aspect 59, wherein the median grain size of the garnet crystals is from about 1 μm to about 2 μm.
[0086] Aspect 61: The composite garnet electrolyte of any one of Aspects 53-60, wherein the electrolyte thickness is 20 μm to 200 μm.
[0087] Aspect 62: The composite garnet electrolyte of any of Aspects 53-61, wherein the composite garnet electrolyte comprises a ring-on-ring strength of about 150 MPa to about 600 MPa.
[0088] Aspect 63: The composite garnet electrolyte of any one of Aspects 53-62, wherein the garnet crystals are doped with tantalum. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] The above features and advantages and other features and advantages of the present disclosure will be better understood by reading the following detailed description with reference to the accompanying drawings, wherein:
[0090] Figure 1 Schematically showing the general structure of a solid-state battery according to aspects of the present disclosure;
[0091] Figure 2 showing a simplified solid-state battery with a solid-state electrolyte according to aspects of the present disclosure;
[0092] Figure 3 Steps are shown in an exemplary method, which includes disposing a precursor on a solid electrolyte to form an anode;
[0093] Figure 4 Steps shown in an exemplary method include disposing a liquid electrolyte above a cathode;
[0094] Figure 5 Steps shown in an exemplary method include disposing a solid electrolyte above a cathode;
[0095] Figure 6 Steps are shown in an exemplary method, which includes etching a first major surface of a solid electrolyte;
[0096] Figure 7 Steps shown in an exemplary method include etching a second major surface of a solid electrolyte;
[0097] Figure 8 The lithium ion conductivity is presented as a function of the lithium content (Li2O wt%) of the garnet;
[0098] Fig. 9 Nyquist plots of Example 1A and Comparative Example AA are shown;
[0099] Fig.10 A scanning electron microscope (SEM) image schematically showing a cross section of Comparative Example BB;
[0100] Fig.11 A scanning electron microscope (SEM) image schematically showing a cross section of Comparative Example AA;
[0101] Fig.12 A scanning electron microscope (SEM) image schematically showing a cross section of Example 3;
[0102] Fig.13 A scanning electron microscope (SEM) image schematically shows the surface of Comparative Example BB;
[0103] Fig.14 A scanning electron microscope (SEM) image schematically showing the surface of Example 2;
[0104] Fig.15 A scanning electron microscope (SEM) image schematically showing the surface of Example 3;
[0105] Fig.16 A scanning electron microscope (SEM) image schematically showing a cross section of Comparative Example BB;
[0106] Fig.17 A scanning electron microscope (SEM) image schematically showing a cross section of Example 2;
[0107] Fig.18 A scanning electron microscope (SEM) image schematically showing a cross section of Example 3;
[0108] Fig.19A scanning electron microscope (SEM) image schematically showing a cross section of Example 4;
[0109] Fig. 20 A scanning electron microscope (SEM) image schematically showing a cross section of Example 5;
[0110] Fig.21 A scanning electron microscope (SEM) image schematically showing a cross section of Example 6;
[0111] Fig. 22 A scanning electron microscope (SEM) image schematically showing a cross section of Example 7;
[0112] Fig.23 A scanning electron microscope (SEM) image schematically showing a cross section of Example 4A;
[0113] Fig.24 A scanning electron microscope (SEM) image schematically showing the surface of Example 4A;
[0114] Fig.25 A scanning electron microscope (SEM) image schematically showing the surface of Example 7A; and
[0115] Fig.26 The pore size distributions of Examples 12-13 and Comparative Examples CC-DD are shown.
[0116] Throughout this disclosure, the drawings are used to emphasize certain aspects. Thus, unless otherwise explicitly stated, it should be assumed that the relative sizes of the various regions, parts, and substrates shown in the drawings are not proportional to their actual relative sizes. DETAILED DESCRIPTION
[0117] Aspects will now be described more fully with reference to the accompanying drawings, in which exemplary aspects are shown. Wherever possible, the same reference numbers are used throughout the drawings to refer to the same or like parts.
[0118] Figure 1-2 A view of a solid-state battery 101 or 201 including a solid-state electrolyte is shown. Unless otherwise stated, a discussion of features for one aspect of a solid-state electrolyte or battery may be equally applicable to corresponding features of any aspect of the present disclosure. For example, throughout the present disclosure, the same part number may indicate that, in some aspects, the features referred to are consistent with each other, and unless otherwise stated, a discussion of the features referred to in one aspect may be equally applicable to the features referred to in any other aspect of the present disclosure.
[0119] Figure 1 The schematic diagram shows the general structure of the solid-state battery 101, and Figure 2A simplified solid-state battery 201 in the form of a button cell is shown. Figure 1 As shown, the solid-state battery 101 or 201 may include, in order: a first current collector 102 (e.g., a substrate), a cathode 104 disposed on the first current collector 102, an optional intermediate layer 114 disposed on the cathode 104, an optional first coating 106, a solid electrolyte 108, an optional second intermediate layer or coating 110, and an anode 112, and a second current collector 116 disposed on the anode 112. Figure 1 As shown, the solid-state battery 101 may optionally include an optional first coating 106 positioned between the cathode 104 and the solid-state electrolyte 108, and / or the solid-state battery 101 may optionally include an optional second intermediate layer or coating 110 positioned between the anode 112 and the solid-state electrolyte 108. Figure 1-2 As shown, the solid electrolyte 108 is positioned between the cathode 104 and the anode 112. The components of the solid-state battery 101 may be arranged in a horizontal relationship or vertically relative to each other.
[0120] The first current collector 102 includes a conductive material. As used herein, the conductive material has a conductivity of 100 Siemens per meter (S / m) measured at 20°C according to ASTME1004-17. In aspects, the first current collector may include: nickel (Ni) foam, carbon fiber, or a solid metal contact (e.g., aluminum, stainless steel, copper, platinum, nickel, gold, zinc, cobalt, nickel, ruthenium, lithium, lead, titanium, nickel-chromium alloy, etc.). In aspects, the first current collector 102 may be a mechanically stable and / or dimensionally stable substrate that supports other elements of the solid-state battery 101 or 201. In aspects, the first current collector 102 may include the same material as the cathode 104 (as described below), so that the first current collector 102 is part of the cathode 104.
[0121] The cathode 104 comprises a conductive material. In aspects, the cathode 104 can be configured to release and recombine cations (e.g., alkali metals: lithium or sodium, alkaline earth metals: magnesium or calcium). In aspects, the cathode 104 can include at least one of an alkali metal (e.g., lithium, sodium) or an alkaline earth metal (e.g., magnesium, calcium). In aspects, the cathode 104 can include one or more of the materials discussed below with respect to the anode 112. In other aspects, the cathode 104 can include the same material as the anode 112. In aspects, the cathode 104 can include a fluoride compound. In other aspects, the cathode 104 can include at least one transition metal, such as: cobalt, manganese, nickel, niobium, tantalum, vanadium, titanium, copper, chromium, tungsten, molybdenum, tin, germanium, antimony, bismuth, iron, or a combination thereof. In aspects, the cathode 104 can include a lithium-based electrode, such as: lithium cobalt oxide (LCO), lithium manganese oxide spinel (LMO), lithium nickel cobalt aluminate (NCA), lithium nickel manganese cobalt oxide (NCM) (LiNi dCo e Mn 1-d-e O2, where 0 < d < 1, 0 < e < 1. For example: LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), etc.), lithium iron phosphate (LiFePO4) (LFP), lithium cobalt phosphate (LCP), lithium titanate, lithium niobium tungstate, nickel lithium manganate, lithium titanium sulfide (LiTiS2), or a combination thereof. In an aspect, the cathode 104 can include a sodium-based electrode, such as: NaVPO4F, NaMnO2, Na 2 / 3 Mn 1-y Mg y O2 (0 < y < 1), Na2Li2Ti5O 12 , Na2Ti3O7, or a combination thereof. In an aspect, the cathode 104 can include a magnesium-based electrode, such as: magnesiochromite (MgCr2O4), MgMn2O4, or a combination thereof. The cathode 104 can be a sintered electrode. Alternatively, the cathode 104 can be unsintered. An exemplary aspect of the cathode 104 is an NCM cathode. In an aspect, the ratio of the weight of the cathode 104 to the cathode surface area (e.g., Figure 5-6 the first major surface 105 of the cathode 104 shown in 2 ) can be: about 5 milligrams per square centimeter (mg / cm 2 ), about 8 mg / cm 2 or greater, about 10 mg / cm 2 or greater, about 15 mg / cm 2 or greater, about 20 mg / cm 2 or greater, about 50 mg / cm 2 or less, about 30 mg / cm 2 or less, about 25 mg / cm 2 or less, about 20 mg / cm 2 or less, or about 15 mg / cm 2 to about 50 mg / cm 2 , about 8 mg / cm 2 to about 30 mg / cm 2 , about 10 mg / cm 2 to about 25 mg / cm 2 , about 15 mg / cm 2 to about 20 mg / cm 2 , or any range or sub-range therebetween.
[0122] like Figure 1 As shown, the solid-state battery 101 may optionally include an intermediate layer 114 positioned between the cathode 104 and the solid-state electrolyte 108. In aspects, the intermediate layer 114 may include a liquid electrolyte (e.g., an ionic liquid, a deep eutectic solvent (DES) or an aprotic solvent). As used herein, an "electrolyte" enables ion transport therein ("ionic conductivity"), and the ionic conductivity corresponds to the conductivity of the electrolyte (e.g., a DES-based electrolyte). The intermediate layer 114 may be liquid at room temperature (i.e., 25°C) and / or at the operating temperature of the solid-state battery 101 (e.g., about 50°C to about 60°C). In aspects, the liquid electrolyte may include a lithium-containing salt and a solvent. In other aspects, the lithium-containing salt may include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiSO3CF3), LiC(SO2CF3)3, or a combination thereof. In other aspects, the concentration of the lithium-containing salt may be about 0.5 molar mass (M) or more, about 1M or more, about 1.2M or more, about 1.5M or more, about 3M or less, about 2.5M or less, or about 2M or less, such as the following range: about 0.5M to about 3M, about 1M to about 3M, about 1.2M to about 2.5M, about 1.5M to about 2M, or any range or sub-range therebetween. An exemplary aspect of the solvent is sulfolane, but other solvents are also possible in other aspects. Providing an intermediate layer 114 containing a liquid electrolyte can wet the interface between the cathode 104 and the solid electrolyte, thereby minimizing the total amount of liquid electrolyte in the solid-state battery 101 while reducing the interfacial resistance therebetween. In one aspect, the cathode surface area (e.g., Figure 5-6 The volume of liquid electrolyte at the first major surface 105 of the cathode 104 shown in FIG. 1 may be about 5 μL / cm 2 or larger, about 8 μL / cm 2 or larger, about 10 μL / cm 2 or larger, about 12 μL / cm 2 or larger, about 15 μL / cm 2 or larger, about 20 μL / cm 2 or smaller, about 15 μL / cm 2 or smaller, about 12 μL / cm 2 or less, or about 10 μL / cm 2 In aspects, the volume range of the liquid electrolyte of the intermediate layer 114 per cathode surface area of the cathode 104 may be: about 5 μL / cm 2 About 20 μL / cm2 , about 8 μL / cm 2 or up to about 15 μL / cm 2 , or about 10 μL / cm 2 up to about 12 μL / cm 2 , or any range or sub-range therebetween.
[0123] As Figure 1-2 shown, solid-state batteries 101 and 201 include a solid electrolyte 108 positioned between a cathode 104 and an anode 112. Throughout this disclosure, "solid-state battery" includes a solid electrolyte. As used herein, a solid electrolyte is a material that is solid at room temperature and at the operating temperature of the solid-state battery (e.g., about 50 °C). In aspects, the solid electrolyte 108 may include an inorganic solid electrolyte. Providing a solid electrolyte can address common safety concerns such as leakage, poor chemical stability, and flammability common in batteries employing liquid electrolytes. Additionally, providing a solid electrolyte can also inhibit the shuttling of polysulfides from the cathode to the anode, resulting in improved electrode (e.g., anode, cathode) utilization as well as high discharge capacity and energy density. Providing a solid electrolyte can reduce the formation of dendrites (e.g., lithium dendrites), which otherwise can lead to battery failure.
[0124] In aspects, the solid electrolyte 108 may include: lithium phosphorus oxynitride (LiPON), lithium garnet (Li7La3Zr2O 12 ), lithium phosphorus sulfide, or combinations thereof. In other aspects, the LIPON material may include Li 3+y PO 4-x N x structures, where y > 0 and 0 < x < 4. In other aspects, the solid electrolyte 108 may comprise: lithium, lanthanum, zirconium, oxygen, or combinations thereof (e.g., each of lithium, lanthanum, zirconium, and oxygen, LIZO compounds). As used herein, "LLZO" refers to a compound comprising lithium, lanthanum, zirconium, and oxygen. In even other aspects, the solid electrolyte 108 may include lithium garnet, such as at least one of the following: (i) Li 7- 3a La3Zr2L a O 12 , L = Al, Ga, or Fe and 0 < a < 0.33; (ii) Li7La 3-b Zr2M b O 12 , M = Bi or Y and 0 < b < 1; (iii) Li 7-c La3(Zr 2-c , N c )O 12, N = In, Si, Ge, Sn, V, W, Te, Nb or Ta and 0 < c < 1; (iv) protonated LLZO (e.g., H x Li 6.5-x La3Zr 1.5 I 0.5 O 12 , I = In, Si, Ge, Sn, V, W, Te, Nb or Ta and 0 < x < 4, or H x Li 6.25- x E 0.25 La3Zr2O 12 , E = Al, Ga or Fe and 0 < x < 4), or a combination thereof. In an aspect, the solid - state electrolyte 108 can include at least one of the following: Li 10 GeP2S 12 , Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 0.55 La 0.35 TiO3, an interpenetrating polymer network (ipn - PEA) electrolyte of poly(ethyl acrylate), a three - dimensional ceramic / polymer network, an in - situ plasticized polymer, a composite polymer of well - aligned ceramic nanofibers, a PEO - based solid polymer, a flexible polymer, a polymeric ionic liquid, in - situ formed Li3PS4, Li6PS5Cl, or a combination thereof. Exemplary aspects of the solid - state electrolyte are doped garnets (e.g., Ta - doped garnets, Al - doped garnets) and undoped garnets, it being understood that the garnets can have excess lithium (over stoichiometry) as described herein.
[0125] As Figure 1-2 shown, the solid - state electrolyte 108 includes a first major surface 109 and a second major surface 107 opposite the first major surface 109, and a thickness of the solid - state electrolyte 108 can be defined between the first major surface 109 and the second major surface 107 (e.g., see Figure 6In aspects, the thickness of the solid electrolyte 108 can be about 20 μm or more, about 40 μm or more, about 60 μm or more, about 80 μm or more, about 100 μm or more, about 150 μm or more, about 300 μm or more, about 500 μm or more, about 600 μm or more, about 700 μm or more, about 800 μm or more, about 1 mm or more, about 2 mm or less, about 1.5 mm or less, about 1.2 mm or less, about 1 mm or less, about 800 μm or less, about 500 μm or less, about 300 μm or less, about 250 μm or less, about 200 μm or less, about 150 μm or less, about 120 μm or less, or about 100 μm or less. In aspects, the thickness of the solid electrolyte 108 can be in the range of about 20 μm to about 2 mm, about 40 μm to about 1.5 mm, about 60 μm to about 1 mm, about 80 μm to about 800 μm, about 100 μm to about 500 μm, about 150 μm to about 300 μm, about 150 μm to about 250 μm, or any range or sub-range therebetween. In aspects, the thickness of the solid electrolyte 108 can be about 300 μm or less, for example, about 20 μm to about 300 μm, about 40 μm to about 250 μm, about 60 μm to about 200 μm, about 80 μm to about 150 μm, about 100 μm to about 150 μm, or any range or sub-range therebetween. In aspects, the thickness of the solid electrolyte 108 can be about 500 μm or greater, such as about 500 μm to about 2 mm, about 600 μm to about 1.5 mm, about 700 μm to about 1 mm, about 800 μm to about 1 mm, or any range or sub-range therebetween.
[0126] In aspects, the solid electrolyte 108 may include a sintered ribbon. As used herein, a sintered ribbon refers to a material formed by sintering a ceramic green body having substantially the same thickness as the solid electrolyte. In other aspects, the solid electrolyte 108 including a sintered ribbon may include a thickness of about 300 μm or less, for example: about 20 μm to about 300 μm, about 40 μm to about 250 μm, about 60 μm to about 200 μm, about 80 μm to about 150 μm, about 100 μm to about 150 μm, or any range or sub-range therebetween. In aspects, the solid electrolyte 108 may include a consolidated granular. As used herein, a solid electrolyte including consolidated granular refers to a material formed by pressing pre-sintered granular together. Compared to a sintered ribbon, the consolidated granular may include larger grains and a greater thickness. In other aspects, the solid electrolyte 108 including consolidated particulates may include a thickness of about 500 μm or greater, for example: about 500 μm to about 2 mm, about 600 μm to about 1.5 mm, about 700 μm to about 1 mm, about 800 μm to about 1 mm, or any range or sub-range therebetween.
[0127] Throughout this disclosure, the Ring-on-Ring (RoR) test is a surface strength measurement used to test flat glass specimens, and ASTM C1499-09 (2013), entitled "Standard Test Method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperature," serves as the basis for the AROR test method described herein. The entire contents of ASTM C1499-09 are incorporated herein by reference. The equibiaxial flexural strength (i.e., the maximum stress that a material can sustain when subjected to flexure between two concentric rings) is determined by placing the sample between two concentric rings of different sizes, with a support ring of diameter D2 supporting the sample. A force F is applied to the surface of the glass-based article via a load ring of diameter D1 by a dynamometer. Unless otherwise specified, the ratio of D1 / D2 is 0.5. The load ring is concentrically aligned with the support ring to within 0.5% of the support ring diameter D2. Under any load, the dynamometer used for the test is accurate to within ±1% of the selected range. The test was carried out at a temperature of 23±2°C and a relative humidity of 40±10%. For the fixture design, the range of the radius r of the protruding surface of the load ring is h / 2≤r≤3h / 2, where h is the thickness of the sample. The load ring and the support ring are made of hardened steel with a hardness of HRc>40. The target failure mechanism of the ROR test is to observe the sample rupture originating from the sample surface area within the two load rings. For data analysis, the failure outside this area (i.e., between the load ring and the support ring) is ignored. However, due to the thinness and high strength of the sample, a large deflection exceeding 1 / 2 sample thickness h is sometimes observed. Therefore, a high percentage of failures originating from below the load ring is often observed. It is impossible to accurately calculate stress without understanding the stress development and failure source of each specimen in the ring and under the ring (collectively referred to as analysis by strain gauges). Therefore, the ROR test focuses on the peak load of failure when measuring the response. As used herein, "ring strength on ring" refers to the strength measured by the ROR test.In aspects, the ring-on-ring strength of the solid electrolyte 108 having a porous surface (e.g., a composite garnet electrolyte having a porous surface) can be: about 150 MPa or greater, about 180 MPa or greater, about 200 MPa or greater, about 220 MPa or greater, about 250 MPa or greater, about 280 MPa or greater, about 300 MPa or greater, about 320 MPa or greater, about 350 MPa or greater, about 380 MPa or greater, about 400 MPa or greater, about 600 MPa or less, about 550 MPa or less, about 500 MPa or less, about 450 MPa or less, about 400 MPa or less, about 350 MPa or less, about 300 MPa or less, or about 250 MPa or less. In aspects, the ring-on-ring strength of the solid electrolyte 108 having a porous surface (e.g., a composite garnet electrolyte having a porous surface) can be in the range of about 150 MPa to about 600 MPa, about 150 MPa to about 550 MPa, about 150 MPa to about 500 MPa, about 150 MPa to about 450 MPa, about 150 MPa to about 400 MPa, about 180 MPa to about 400 MPa, about 200 MPa to about 350 MPa, about 220 MPa to about 350 MPa, about 250 MPa to about 300 MPa, about 280 MPa to about 300 MPa, or any range or sub-range therebetween. Having a sintered tape as a solid electrolyte (e.g., a composite garnet electrolyte) can achieve high ring-on-ring strength (e.g., about 150 MPa or more or about 150 MPa to about 400 MPa).
[0128] Throughout the present disclosure, the amount of lithium (e.g., LiO weight %, calculated as oxide and based on the solid electrolyte (composite garnet electrolyte, composite garnet electrolyte with porous surface) as 100 weight %) is determined based on flame emission spectroscopy of a material sampled from the center of the sample (i.e., a material located halfway between the first major surface and the second major surface). Without wishing to be bound by theory, the stoichiometric ratio of garnet (e.g., 0.5 Ta-doped LLZO, Li 6.5 LqCy 1.5 Ta 0.5 O 12) would be about 11.1 wt % Li2O, calculated as oxide. As used herein, "calculated as oxide" means that when the component is measured, it is as if the non-oxygen components in the compound are converted to a specified oxide form or a fully oxidized oxide (if a specific oxide form is not specified). For example, sodium (Na) calculated as oxide refers to the amount of sodium oxide (Na2O), while lithium calculated as oxide refers to the amount of lithium oxide (Li2O). Thus, for the measurement of a component "calculated as oxide", the component does not need to actually be a specific oxide form or a fully oxidized oxide. Thus, for the measurement of a specific component "calculated as oxide", it is included that the material containing the non-oxygen element of the specific component is conceptually converted to a specified oxide form or a fully oxidized oxide (if a specific oxide form is not specified before calculating the concentration as oxide). As described above, the amount of lithium is determined based on flame emission spectroscopy, which means that the amount of lithium refers to the actual amount of lithium in the resulting solid electrolyte (e.g., a composite garnet electrolyte). This is different from the amount of lithium that can be added to the garnet crystals before firing (e.g., sintering) to form a solid electrolyte, because lithium is known to volatilize during firing. As described in the examples below, adjusting the firing conditions themselves will change the amount of lithium present in the resulting solid electrolyte.
[0129] In aspects, the solid electrolyte 108 (e.g., a composite garnet electrolyte, a composite garnet electrolyte having a porous surface) may have an amount of lithium (e.g., in terms of oxide, Li2O) greater than the stoichiometric amount of lithium, for example, about 0.1 wt% or more, about 0.2 wt% or more, about 0.3 wt% or more, about 0.4 wt% or more, about 0.5 wt% or more, about 0.6 wt% or more, about 0.7 wt% or more, about 0.8 wt% or more, about 4 wt% or less, about 3.5 wt% or less, about 3.0 wt% or less, about 2.5 wt% or less, about 2.0 wt% or less, about 1.5 wt% or less, about 1.2 wt% or less, about 1.0 wt% or less, about 0.9 wt% or less, about 0.8 wt% or less, based on 100 wt% of the solid electrolyte. In aspects, the solid electrolyte 108 (e.g., a composite garnet electrolyte, a composite garnet electrolyte having a porous surface) may have a lithium amount (e.g., Li2O in terms of oxide) greater than the stoichiometric lithium amount, for example, from about 0.1 wt% to about 4.0 wt%, from about 0.1 wt% to about 3.5 wt%, from about 0.1 wt% to about 3.0 wt%, from about 0.2 wt% to about 2.5 wt%, from about 0.2 wt% to about 2.0 wt%, from about 0.2 wt% to about 1.5 wt%, from about 0.3 wt% to about 1.2 wt%, from about 0.3 wt% to about 1.0 wt%, from about 0.3 wt% to about 0.9 wt%, from about 0.4 wt% to about 0.8 wt%, from about 0.5 wt% to about 0.8 wt%, from about 0.5 wt% to about 0.8 wt%, or any range or sub-range therebetween, based on 100 wt% of the solid electrolyte. In aspects, the amount of lithium (e.g., in terms of oxide, Li2O) of the solid electrolyte 108 (e.g., a composite garnet electrolyte, a composite garnet electrolyte having a porous surface) can be about 11.2 wt% or more, about 11.3 wt% or more, about 11.4 wt% or more, about 11.5 wt% or more, about 11.6 wt% or more, about 11.7 wt% or more, about 11.8 wt% or more, about 11.9 wt% or more, about 12.1 wt% or more, about 12.2 wt% or more, about 12.3 wt% or more, about 12.4 wt% or more, about 12.5 wt% or more, about 12.6 wt% or more, about 12.7 wt% or more, about 12.8 wt% or more, about 12.9 wt% or more, about 12.1 wt% or more, about 12.1 wt% or more, about 12.2 wt% or more, about 12.3 wt% or more, about 12.4 wt% or more, about 12.5 wt% or more, about 12.6 wt% or more, about 12.7 wt% or more, about 12.8 wt% or more, about 12.9 wt% or more, about 12.0 wt % or more, about 15 wt % or less, about 14.5 wt % or less, about 14.0 wt % or less, about 13.5 wt % or less, about 13.0 wt %, about 12.5 wt % or less, about 12.2 wt % or less, about 12.1 wt % or less, about 12.0 wt % or less, about 11.9 wt % or less, about 11.8 wt % or less, about 11.7 wt % or less, about 11.6 wt % or less, or about 11.5 wt % or less.In aspects, the amount of lithium (e.g., Li2O in terms of oxide) of the solid electrolyte 108 (e.g., a composite garnet electrolyte, a composite garnet electrolyte having a porous surface), based on 100 wt% of the solid electrolyte, can be in the range of about 11.2 wt% to about 15 wt%, about 11.2 wt% to about 14.5 wt%, about 11.2 wt% to about 14.0 wt%, about 11.3 wt% to about 13.5 wt%, about 11.3 wt% to about 13.0 wt%, about 11.3 wt% to about 12.5 wt%, about 11.3 wt% to about 12.2 wt%, about 11.4 wt% to about 12.1 wt%, about 11.4 wt% to about 12.0 wt%, about 11.5 wt% to about 11.9 wt%, about 11.6 wt% to about 11.8 wt%, or any range or sub-range therebetween. Thus, in aspects, the solid electrolyte 108 (e.g., a composite garnet electrolyte, a composite garnet electrolyte having a porous surface) can include a composite having a lithium phase between garnet crystals. In aspects, a preferred range of lithium amounts can be: about 11.2 wt % to about 15 wt %, about 11.3 wt % to about 12.2 wt %, or about 11.4 wt % to about 12.0 wt %. As discussed herein, providing excess lithium (relative to the stoichiometric ratio) in the composite garnet electrolyte can promote the formation of a mixture of intergranular and transgranular microstructures and can promote etching of the composite garnet electrolyte to form a porous surface of the composite garnet electrolyte.
[0130] Throughout this disclosure, cross-sectional SEM images of solid electrolytes produced by fracturing the solid electrolyte (e.g., Figure 10-12 and 16-24 extend along the thickness direction) analysis to determine the microstructure of the solid electrolyte. As used herein, "through-grain microstructure" refers to the situation when the fracture propagates through the crystal grains of garnet. As used herein, "inter-granular microstructure" refers to the situation when there is a fracture along the grain boundary between the crystal grains of garnet. Due to the fracture along the grain boundary for the inter-granular microstructure, the SEM image shows more limited shapes related to the crystal grains than the through-grain microstructure (e.g., "rock candy" structure). As used herein, the microstructure extending from the surface of the electrolyte to a certain depth means that the continuous path from the surface through the electrolyte includes the specific microstructure. Therefore, there will be multiple microstructures in the electrolyte (or even presented as a common distance from the surface, and one of the microstructures extends to a depth greater than the common distance, if there is a continuous path to the depth in the microstructure).
[0131] In one embodiment, the solid electrolyte 108 (eg, a composite garnet electrolyte, a composite garnet electrolyte having a porous surface) may include an intergranular microstructure extending from a first major surface 109 of the solid electrolyte to a first distance. Fig.18 As shown, the composite garnet electrolyte 1801 may include an intergranular microstructure 1807 extending from a first major surface 1805 of the composite garnet electrolyte 1801 to a depth 1813. In other aspects, the thickness of the electrolyte is measured as a percentage (see Figure 6 In other aspects, the first distance that the intergranular microstructure extends from the first major surface can be, as a percentage of the electrolyte thickness 607, about 5% or more, about 10% or more, about 15% or more, 18% or more, 20% or more, 22% or more, 25% or more, 27% or more, 30% or more, 40% or less, 35% or less, 32% or less, 30% or less, 28% or less, or 25% or less. In other aspects, the first distance that the intergranular microstructure extends from the first major surface can be, as a percentage of the electrolyte thickness, in the range of about 5% to about 40%, about 10% to about 40%, about 15% to about 40%, about 18% to about 40%, about 20% to about 35%, about 20% to about 32%, about 22% to about 30%, about 25% to about 28%, or any range or sub-range therebetween. In other aspects, the first distance that the inter-grain microstructure extends from the first major surface can be: 2μm or greater, 4μm or greater, 6μm or greater, 8μm or greater, 10μm or greater, 12μm or greater, 15μm or greater, 20μm or greater, 25μm or greater, 30μm or greater, 40μm or greater, 100μm or less, 70μm or less, 50μm or less, 40μm or less, 30μm or less, 25μm or less, 20μm or less, 18μm or less, 15μm or less, 12μm or less, 10μm or less. In other aspects, the first distance that the inter-grain microstructure extends from the first major surface can be in the range of 2 μm to 100 μm, 4 μm to about 70 μm, 6 μm to 50 μm, 8 μm to 40 μm, 10 μm to 30 μm, 12 μm to 25 μm, 15 μm to 20 μm, or any range or sub-range therebetween. Fig.18 , composite garnet electrolyte 1801 can include regions of intergranular microstructures 1807 and 1809 extending from corresponding major surfaces of composite garnet electrolyte 1801. In addition, as shown, composite garnet electrolyte 1801 can include regions of through-grain microstructure 1811 sandwiched between regions having intergranular microstructures 1807 and 1809. Providing a through-grain microstructure near and / or at the first major surface can facilitate the formation of large and / or deep pores therein.
[0132] Throughout the present disclosure, the grain size of garnet (e.g., of a solid electrolyte) is determined according to ASTM E112-13. In aspects, the median grain size of the garnet can be about 3.0 μm (e.g., 3 μm) or less, about 2.9 μm or less, about 2.7 μm or less, about 2.5 μm or less, about 2.3 μm or less, about 2.0 μm or less, about 1.8 μm or less, about 1.5 μm or less, about 1.3 μm or less, about 1.0 μm or less, about 1.0 μm (e.g., 1 μm) or more, about 1.1 μm or more, about 1.3 μm or more, about 1.5 μm or more, about 1.7 μm or more, or about 2.0 μm or more. In aspects, the median grain size of the garnet can be in the range of about 1.0 μm to about 4.0 μm, about 1.0 μm to about 3.0 μm (e.g., about 1 μm to about 3 μm), about 1.0 μm to about 2.9 μm, about 1.1 μm to about 2.7 μm, about 1.1 μm to about 2.5 μm, about 1.3 μm to about 2.3 μm, about 1.3 μm to about 2.0 μm, about 1.3 μm to about 1.8 μm, or any range or sub-range therebetween. Providing a grain size of about 3 μm or less, about 1 μm to about 3 μm, or about 1 μm to about 2 μm can enable increased ionic conductivity, for example by reducing the path length along the grain boundaries along which ions transported through the solid electrolyte sheet move and / or by providing additional grain boundaries per unit volume of the solid electrolyte.
[0133] As discussed below, a composite garnet electrolyte (e.g., a solid electrolyte 108 with a porous surface) can be formed by etching at least the first major surface 109. Without being limited by theory, it is believed that etching may be preferentially etching the lithium phase between the grains in the composite garnet electrolyte in the region with intergranular microstructure, so that the composite garnet electrolyte of the present disclosure can be more easily and / or more quickly etched than other garnet electrolytes (e.g., with a stoichiometric lithium amount). Throughout the present disclosure, the porosity and / or pore size distribution of the solid electrolyte are determined according to ASTME1245-03. The pores can extend from at least the first major surface 109 of the solid electrolyte 108, and in other aspects, the pores can extend from the first major surface 109 and the second major surface 107 at the same time.
[0134] In aspects, the median pore size of the solid electrolyte can be about 0.25 μm or more, about 0.5 μm or more, about 1.0 μm (e.g., about 1 μm) or more, about 1.3 μm or more, about 1.5 μm or more, about 1.7 μm or more, about 2.0 μm or more, about 2.2 μm or more, about 2.5 μm or more, about 3.0 μm or more, about 4.0 μm or more, about 5.0 μm or more, about 6.0 μm or more, about 8.0 μm or more. m or greater, about 10 μm or greater, about 12 μm or greater, about 14 μm or greater, about 20 μm or less, about 17 μm or less, about 15 μm or less, about 12 μm or less, about 10 μm or less, about 7 μm or less, about 5 μm or less, about 3.0 μm (e.g., about 3 μm) or less, about 2.8 μm or less, about 2.6 μm or less, about 2.4 μm or less, about 2.2 μm or less, or about 2.0 μm or less. In aspects, the median pore size of the solid electrolyte can be in the range of about 0.25 μm to about 20 μm, about 0.5 μm to about 20 μm, about 1 μm to about 20 μm, about 1.3 μm to about 20 μm, about 1.5 μm to about 20 μm, about 1.7 μm to about 20 μm, about 2.0 μm to about 20 μm, about 2.2 μm to about 20 μm, about 2.5 μm to about 20 μm, about 3 μm to about 20 μm, about 4 μm to about 17 μm, about 5 μm to about 15 μm, about 6 μm to about 12 μm, about 8 μm to about 10 μm, or any range or sub-range therebetween. In aspects, the median pore size of the solid electrolyte can be about 5 μm or greater, such as the following range: about 5.0 μm to about 20 μm, about 6.0 μm to about 20 μm, about 8.0 μm to about 20 μm, about 10 μm to about 17 μm, about 12 μm to about 17 μm, about 14 μm to about 15 μm, or any range or sub-range therebetween. In aspects, the median pore size of the solid electrolyte can be about 5 μm or less, such as the following range: about 0.25 μm to about 5.0 μm, about 0.5 μm to about 5.0 μm, about 1.0 μm to about 5.0 μm, about 1.0 μm to about 4.0 μm, about 1.0 μm to about 3.0 μm, about 1.3 μm to about 3.0 μm, about 1.5 μm to about 3.0 μm, about 1.5 μm to about 2.8 μm, about 1.8 μm to about 2.5 μm, about 1.8 μm to about 2.4 μm, about 2.0 μm to about 2.2 μm. For example, as described below with reference to Fig.26 As discussed, the composite garnet electrolyte with a porous surface according to the present disclosure may have a median pore size greater than that of the comparative example. For example, the median pore size of the porous surface of the composite garnet electrolyte according to the present disclosure is 0.25 μm or greater, for example: 0.25 μm to 20 μm, 1 μm to 20 μm, or 3 μm to 20 μm.
[0135] In aspects, the average depth of the pores can be about 2 μm or more, about 5 μm or more, about 7 μm or more, about 10 μm or more, about 15 μm or more, about 20 μm or more, about 25 μm or more, about 30 μm or more, about 35 μm or more, about 40 μm or more, about 50 μm or more, about 60 μm or less, about 55 μm or less, about 50 μm or less, about 45 μm or less, about 40 μm or less, about 35 μm or less, about 30 μm or less, about 25 μm or less, or about 20 μm or less. In aspects, the average depth of the pores can be in the range of about 2 μm to about 60 μm, about 5 μm to about 55 μm, about 8 μm to about 50 μm, about 10 μm to about 45 μm, about 15 μm to about 40 μm, about 20 μm to about 35 μm, about 25 μm to about 30 μm. In aspects, the average depth of the pores can be about 20 μm or greater, such as in the range of about 20 μm to about 60 μm, about 25 μm to about 55 μm, about 30 μm to about 50 μm, about 35 μm to about 45 μm, about 40 μm to about 45 μm, or any range or sub-range therebetween. In aspects, the average depth of the pores can be in the range of about 2 μm to about 60 μm, about 25 μm to about 55 μm, about 30 μm to about 50 μm, about 35 μm to about 45 μm, about 40 μm to about 45 μm, or any range or sub-range therebetween. In aspects, the average depth of the pores can be in the range of about 1 μm to about 20 μm, about 1 μm to about 60 μm, about 25 μm to about 55 μm, about 30 μm to about 50 μm, about 35 μm to about 45 μm, about 40 μm to about 45 μm, or any range or sub-range therebetween. In aspects, the average depth of the pores can be in the range of about 1 μm to about 60 μm, about 1 μm to about 60 μm, about 25 μm to about 55 μm, about 30 μm to about 50 μm, about 35 μm to about Figure 6 In aspects, the average depth of the pores, as a percentage of the electrolyte thickness 607, can be in the range of about 5% to about 30%, about 8% to about 25%, about 10% to about 20%, about 12% to about 17% by weight, about 15% to about 17% by weight, about 20% to about 30%, about 25% to about 20%, about 17% to about 15%, about 12% to about 17%, or about 10% to about 17%, or any range or sub-range therebetween. Providing deep pores (e.g., about 2 μm or greater, about 20 μm to about 60 μm, about 5% of the electrolyte thickness or greater, or about 10% to about 20% of the electrolyte thickness) can increase the effective surface area of the solid electrolyte (e.g., facing the anode and / or facing the cathode), which can reduce the interfacial resistance of a battery comprising a solid electrolyte having a porous surface (e.g., a composite garnet electrolyte having a porous surface).
[0136] In aspects, the optional first coating 106 may include: a carbon-based intermediate layer (e.g., interconnected free-standing, containing micropores / mesoporous, functionalized, biomass-derived), a polymer-based intermediate layer, a metal-based coating (e.g., Ni foam, etc.), a liquid electrolyte (e.g., LiPF6 in ethyl carbonate (EC) / dimethyl carbonate (DMC)), an ionic liquid-based (e.g., LiCF3SO3 / CH3CONH2, LiTFSI / N-methylacetamide (NMA), PEO 18 LiTFSI-10%SiO2-10%IL, etc., wherein LiTFSI is bis(trifluoromethane)sulfonyl imide lithium salt (LiN(CF3SO2)2), SiO2 can be nanoparticles, and IL is an ionic liquid), or a combination thereof. Exemplary aspects of polymer-based intermediate layers include: carbon polysulfide (CS), polyethylene oxide (PEO), polyaniline (PANI), polypyrrole (PPY), poly(3,4-ethylenedioxythiophene) (PEDOT), poly(styrene sulfonic acid) (PSS), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyallylamine hydrochloride (PAH), poly(vinylidene fluoride-co-hexafluoropropylene) (P(VDF-co-HFP)), poly(methyl methacrylate) (PMMA), polyvinylidene fluoride (PVDF), poly(diallyldimethylammonium)bis(trifluoromethanesulfonyl)imide (TFSI) (PDDATFSI), or a combination thereof. In aspects, the optional first coating 106 can include at least one, at least two, or at least three elements selected from the group consisting of nitrogen, carbon, cobalt, titanium, tantalum, and tungsten.
[0137] In aspects, the optional second intermediate layer or coating 110 may include materials or aspects discussed above with respect to the optional first coating 106 and / or intermediate layer 114. In aspects, the optional second intermediate layer or coating 110 may include an anode protectant, such as: an electrolyte additive (e.g., LiNO3, lanthanum nitrate, copper acetate, P2S5, etc.), an artificial interface layer (e.g., Li3N, (CH3)3SiCl, Al2O3, LiAl, etc.), a composite metal (e.g., Li7B6, Li-rGO (reduced graphene oxide), layered Li-rGO, etc.), or a combination thereof. In aspects, the optional second intermediate layer or coating 110 may include a thin layer of a metal (e.g., Au) that may be ion sputtered to form a contact interface between the cathode 112 of the solid electrolyte 108 and another material of the optional second intermediate layer or coating 110. In aspects, the optional second intermediate layer or coating 110 may include a lithium fluoride coating. In aspects, as Figure 2 As shown, the solid-state battery 201 may not have the optional second intermediate layer or second coating so that the anode 112 contacts the solid-state electrolyte 108.
[0138] like Figure 1-2 As shown, the anode 112 can be disposed on the solid electrolyte 108. In one aspect, as Figure 2 As shown, the first major surface 113 of the anode 112 can be arranged on the first major surface 109 of the solid electrolyte 108. As shown, the anode 112 includes a second major surface 115 opposite the first major surface 113, and the anode thickness 119 is defined as the average distance therebetween when the solid-state battery 201 is in a fully charged state (as defined below). In aspects, the anode thickness 119 can be: about 1 micrometer (μm) or more, about 10 μm or more, about 50 μm or more, about 100 μm or more, about 150 μm or more, about 500 μm or less, about 400 μm or less, about 300 μm or less, or about 250 μm or less. In aspects, anode thickness 119 can be in a range of about 1 μm to about 500 μm, about 10 μm to about 400 μm, about 50 μm to about 300 μm, about 100 μm to about 300 μm, about 150 μm to about 250 μm, or any range or sub-range therebetween.
[0139] Anode 112 is a lithium-containing anode. In aspects, the lithium-containing anode may be substantially composed of lithium metal. Alternatively, in aspects, the lithium-containing anode may include an alloy of lithium with at least one of magnesium (Mg), silver (Ag), or a combination thereof. In aspects, the lithium-containing alloy may also include a second component selected from the group consisting of calcium (Ca), aluminum (Al), gallium (Ga), boron (B), carbon (C), silicon (Si), tin (Sn), zinc (Zn), indium (In), antimony (Sb), silver (Ag), and combinations thereof. Exemplary aspects of the second component include: calcium (Ca), tin (Sn) and silver (Ag). Providing a lithium-containing anode comprising a lithium alloy can increase the wettability of the anode on the coating, which can reduce the interfacial resistance of the battery (e.g., by achieving and / or maintaining good contact with a solid electrolyte via the coating), can promote high area capacitance of the battery, and / or can promote high charging current density of the battery.
[0140] Figure 2 A solid-state battery 201 is shown. Figure 2 As shown, the solid-state battery 201 may include a button cell form, but in other aspects, the battery may include another form. Figure 1 , Figure 2 is a simplified solid-state battery 201 because the optional first coating 106 is omitted. Thus, for example, the intermediate layer 114 can be in direct contact with the cathode 104 and the solid-state electrolyte 108 because the optional first coating 106 is omitted. In aspects such as Figure 2As shown, the area of the first major surface 113 of the anode 112 can be less than or equal to (e.g., less than) the area of the first major surface 109 of the solid electrolyte 108. In other aspects, as shown, the area of the first major surface 113 of the anode 112 can be substantially equal to the corresponding area of the cathode 104. Alternatively, as shown Figure 1 As shown, the area of the first major surface 113 of the anode 112 can be substantially equal to the area of the first major surface 109 of the solid electrolyte 108. Figure 2 As shown, electrical insulating layers 205a and 205b may be placed between first current collector 102 and second current collector 116 to prevent short circuits in solid-state battery 201 and / or form a barrier to protect the contents of solid-state battery 201. As used herein, electrical insulating layers 205a and 205b include 10 -5 S / cm or lower conductivity. In even other aspects, as shown, electrical insulating layers 205a and 205b can be configured to maintain the structure of solid-state battery 201, for example, by preventing solid electrolyte 108 from contacting second current collector 116. In other aspects, electrical insulating layers 205a and 205b may include polymer materials, such as: fluoropolymers, rubber, polyurethane or silicone. In aspects, as shown, solid-state battery 201 may also include a conductive spacer 203 placed between anode 112 and second current collector 116. In other aspects, conductive spacer 203 may include foam (e.g., Ni foam), which can help maintain contact between adjacent components of the solid-state battery and / or control the amount of stress experienced by the components of the solid-state battery. Although not shown, a conductive spacer may be placed between the cathode and the first current collector.
[0141] As used herein, "interface resistance" and "ionic conductivity" are measured using electrical impedance spectroscopy (EIS) at 25°C for frequencies between 0.1 Hz and 1 megahertz (MHz). Unless otherwise specified, EIS is measured using a Solartron 1260A (Solartron Corporation) impedance analyzer. Nyquist plots are constructed with the real part of the impedance (Z', measured in Ωcm) on the horizontal axis. 2 ) and the vertical axis is the imaginary part of impedance (Z), measured in Ωcm 2 ). Throughout this disclosure, "interface resistance" is defined as the difference between the real part of the impedance at the endpoints of the arc in the EIS result (i.e., Nyquist plot), where the higher endpoint is considered to be the inflection point in the impedance result. To determine the "interface resistance", the battery is constructed to use a lithium-containing anode disposed on a first major surface of the solid electrolyte and a second major surface of the solid electrolyte facing the cathode. In aspect, the interface resistance can be: about 60Ωcm 2 Or less, about 50Ωcm 2 Or less, about 40Ωcm2 Or less, about 30Ωcm 2 Or less, about 25Ωcm 2 or less, or about 20Ωcm 2 In one aspect, the interface resistance may be in the following range: about 10 Ωcm 2 to about 60Ωcm 2 , about 10Ωcm 2 to about 50Ωcm 2 , about 10Ωcm 2 to about 40Ωcm 2 , about 15Ωcm 2 to about 30Ωcm 2 , about 20Ωcm 2 to about 25Ωcm 2 , or any range or sub-range therebetween.
[0142] Unless otherwise specified, cycling includes charging at 1C to a predetermined nominal areal capacity and discharging at 0.5C when the battery is maintained at 60°C. As used herein, "nominal capacity" (e.g., nominal areal capacity) refers to the capacity achieved using predetermined charging conditions in the first charging step of the battery. The areal capacity is presented based on the surface area of the anode. Unless otherwise specified, battery testing including capacity retention and cycling of various nominal areal capacities is performed at 60°C using a battery test system CT2001A (Landt Corporation). In aspect, the battery can withstand at least 10 cycles of: at 60°C, 1.6 mA / cm 2 (1.6C) or greater, about 1.8mA / cm 2 (1.8C) or greater or about 2mA / cm 2 (1.8C) charging current density reaches 1mAh / cm 2 The nominal area capacity and 0.5 mA / cm 2 (0.5C) discharge current density. As used herein, "survive" means that the battery does not exhibit short circuit or non-ohmic behavior during cycling. In one aspect, the battery can survive at least 50 cycles of: at 60°C, at 1.6 mA / cm 2 (1.6C) or greater, about 1.8mA / cm 2 (1.8C) or greater or about 2mA / cm 2 (1.8C) charging current density reaches 1mAh / cm 2 The nominal area capacity and 0.5 mA / cm 2 In one aspect, the battery can withstand at least 70 cycles of: at 60°C, at 1.6 mA / cm 2(1.6C) or greater, about 1.8mA / cm 2 (1.8C) or greater or about 2mA / cm 2 (1.8C) charging current density reaches 1mAh / cm 2 The nominal area capacity and 0.5 mA / cm 2 (0.5C) discharge current density.
[0143] Throughout this disclosure, "critical current density" refers to the maximum current density that a solid lithium-containing battery can tolerate without causing damage or degradation of the solid electrolyte or other components. Unless otherwise stated, the "critical current density" is determined using the same battery cycling conditions (e.g., using the battery test system CT2001A (Landt) at 60°C), except that a different current density is used for the current density to be tested. In aspect, the critical current density of a solid-state battery containing a solid electrolyte with a porous surface (e.g., a composite garnet electrolyte with a porous surface) can be: about 2 mA / cm 2 or greater, about 2.5mA / cm 2 or greater, about 3mA / cm 2 or greater, about 3.5mA / cm 2 or greater, about 4mA / cm 2 or greater, about 4.5mA / cm 2 or greater, or about 5mA / cm 2 or larger.
[0144] Will refer to Figure 3-7 The exemplary method steps shown discuss aspects of a method for processing a solid-state battery and / or a method for manufacturing a solid-state battery according to aspects of the present disclosure. The method may include providing a solid-state electrolyte comprising one or more of the materials discussed above with reference to the solid-state electrolyte. In aspects, the solid-state electrolyte may include a sintered strip, for example, having a thickness of about 20 μm to about 300 μm. Alternatively, in aspects, the solid-state electrolyte may be formed (e.g., to form a sintered strip) as discussed below in the present disclosure.
[0145] In aspects, the method may include forming a garnet powder, but in other aspects the garnet powder may be provided (e.g., by purchase). In other aspects, stoichiometric amounts of component materials (e.g., Li2CO3 for Li, La2O3 for La, ZrO2 for Zr), including any selected dopant (e.g., Ta, In, Si, Ge, Sn, V, W, Te, Nb and / or other dopants discussed above) are mixed with a slight excess (e.g., about 2 wt% excess) of lithium (added as a super addition to compensate for volatilization during heating). The mixture may be mixed with (e.g., ground with) a grinding medium (e.g., yttrium-stabilized zirconia balls) and an optional solvent (e.g., isopropanol) to homogenize the mixture. In even other aspects, the mixture may include a Ta source as a dopant. In other aspects, the mixture can be calcined at a calcination temperature of about 800° C. to about 1200° C. (e.g., 850° C. to about 1200° C., 900° C. to 1100° C., or any range or sub-range therebetween) for a calcination time of about 2 hours to about 12 hours (e.g., about 4 hours to about 8 hours) to form a garnet powder.
[0146] In aspects, the method may include casting a green ribbon comprising garnet, excess lithium, a binder, and a solvent, although in other aspects the green ribbon (or untreated garnet electrolyte) may also be provided (e.g., by purchase). In other aspects, the amount of excess lithium, in % by weight of the amount of garnet, may be greater than 0.5 wt%, about 2 wt% or more, about 5 wt% or more, about 10 wt% or more (e.g., greater than 10 wt%), about 15 wt% or more, about 18 wt% or more, about 20 wt% or more, about 22 wt% or more, about 25 wt% or more, about 27 wt% or more, about 30 wt% or more, about 50 wt% or less, about 45 wt% or less, about 40 wt% or less, about 35 wt% or less, about 30 wt% or less, about 27 wt% or less, or about 25 wt% or less. In aspects, the amount of excess lithium, in terms of weight percent of the amount of garnet, can be in the range of greater than 0.5 wt % to 50 wt %, 2 wt % to 50 wt %, 5 wt % to 50 wt %, 10 wt % to 50 wt % (e.g., greater than 10 wt % to 50 wt %), 15 wt % to 50 wt %, 18 wt % to 50 wt %, 20 wt % to 50 wt %, about 22 wt % to 45 wt %, 22 wt % to 40 wt %, 25 wt % to 35 wt %, 27 wt % to 30 wt %, or any range or sub-range therebetween. Providing excess lithium in excess of 0.5 wt %, in excess of 2 wt %, or in excess of 10 wt % can achieve: forming a mixture of intergranular and transgranular microstructures, a grain size of about 3 μm or less (e.g., 1 μm to 3 μm or 1 μm to 2 μm), and / or can facilitate etching of the composite garnet electrolyte to form a composite garnet electrolyte having a porous surface. The combination of firing conditions and excess lithium determines the amount of lithium that remains in the resulting electrolyte. If the firing temperature is too high (e.g., greater than 1200° C.) and / or the duration is too long (e.g., greater than 60 minutes, depending on the temperature), the vast majority of the excess lithium added to the green strip will volatilize, resulting in an electrolyte that does not have a transgranular microstructure unlike aspects of the present disclosure.
[0147] In other aspects, the method can include firing the green strip at a firing temperature for a firing period to form an untreated solid electrolyte (e.g., an untreated garnet electrolyte). In even other aspects, the firing temperature can be about 900°C or more, about 950°C or more, about 980°C or more, about 1000°C or more, about 1030°C or more, about 1050°C or more, about 1080°C or more, about 1100°C or more, about 1200°C or less, about 1160°C or less, about 1150°C or less, about 1130°C or less, about 1100°C or less, about 1080°C or less, or about 1050°C or less. In even other aspects, the firing temperature can be in the range of about 900°C to about 1200°C, about 900°C to about 1160°C, about 900°C to about 1150°C, about 950°C to about 1150°C, about 980°C to about 1120°C, about 1000°C to about 1120°C, about 1030°C to about 1100°C, about 1050°C to about 1080°C, or any range or sub-range therebetween. In even other aspects, the firing time period can be 5 minutes or more, 8 minutes or more, 10 minutes or more, 12 minutes or more, 15 minutes or more, 20 minutes or more, 60 minutes or less, 45 minutes or less, 40 minutes or less, 35 minutes or less, 30 minutes or less, 25 minutes or less, 22 minutes or less, 20 minutes or less, 18 minutes or less, or 15 minutes or less. In even other aspects, the firing time period can be in the range of 5 minutes to 60 minutes, 5 minutes to 45 minutes, 8 minutes to 40 minutes, 10 minutes to 35 minutes, 12 minutes to 30 minutes, 15 minutes to 25 minutes, 18 minutes to 22 minutes, or any range or sub-range therebetween. In even other aspects, the firing time period can be 30 minutes or less, such as in the range of 5 minutes to 30 minutes, 8 minutes to 25 minutes, 10 minutes to 22 minutes, 12 minutes to 20 minutes, 15 minutes to 18 minutes, or any range or sub-range therebetween. The resulting solid electrolyte (e.g., an untreated solid electrolyte, an untreated garnet electrolyte) can include: a lithium amount having one or more corresponding ranges discussed above (e.g., about 11.2 wt. % to about 15 wt. %, about 11.3 wt. % to about 12.2 wt. %, or about 11.4 wt. % to about 12 wt. %); a mixture of intergranular and transgranular microstructures (e.g., the transgranular microstructure extends to a depth of about 25% or greater of the electrolyte thickness or any corresponding range discussed above); and / or a lithium phase between garnet grains (e.g., intergranular microstructure).
[0148] In aspects, untreated solid electrolyte (e.g., untreated garnet electrolyte) can be contacted with water before etching (see next paragraph). In other aspects, untreated solid electrolyte can be contacted with water for a time period of at least 1 minute, such as: 1.5 minutes or longer, 2 minutes or longer, 3 minutes or longer, 4 minutes or longer, 5 minutes or longer, 7 minutes or longer, 10 minutes or longer, 8 hours or shorter, 2 hours or shorter, 1 hour or shorter, 45 minutes or shorter, 30 minutes or shorter, 20 minutes or shorter, 15 minutes or shorter, or 10 minutes or shorter. In other aspects, untreated solid electrolyte can be contacted with water for a time period of the following range: at least 1 minute to 8 hours, at least 1 minute to 2 hours, at least 1 minute to 1 hour, 1.5 minutes to 45 minutes, 2 minutes to 30 minutes, 3 minutes to 20 minutes, 4 minutes to 15 minutes, 5 minutes to 10 minutes, or any range or sub-range therebetween. For example, as discussed in the embodiments, the untreated solid electrolyte can be in contact with water (e.g., deionized water) for about 10 minutes. In other aspects, the water can be deionized water or ultrapure water. In other aspects, the water temperature can be: about 15 ° C or higher, about 20 ° C or higher, about 22 ° C or higher, about 25 ° C or higher, about 40 ° C or lower, about 30 ° C or lower, about 27 ° C or lower, or about 25 ° C or lower, such as the following range: about 15 ° C to about 40 ° C, about 20 ° C to about 30 ° C, about 22 ° C to about 27 ° C, or any range or sub-range therebetween. Without being limited to theory, the contact of the solid electrolyte (e.g., untreated solid electrolyte or untreated garnet electrolyte) produces a surface layer of protonized garnet on the solid electrolyte.
[0149] In terms of Figure 6 As shown, the method may include etching at least the first major surface 109 of the solid electrolyte 108 (e.g., the composite garnet electrolyte) with an etchant 603 (e.g., an acid) to form a porous surface of the composite garnet electrolyte containing pores (e.g., Figure 1-2603). In other aspects, as shown, when the first major surface 109 of the solid electrolyte 108 is in contact with the etchant 603, the etchant 603 can be contained in the container 601, but the etchant can also be dispensed from the container onto the first major surface (e.g., by spraying). In other aspects, the acid of the etchant 603 can be an inorganic acid (e.g., HCl, HNO3, H2SO4). An exemplary aspect of the etchant is HCl. In other aspects, the acid concentration in the etchant 603 can be: about 0.5M or more, about 0.6M or more, about 0.8M or more, about 1.0M or more, about 1.2M or more, about 1.5M or more, about 1.8M or more, about 2M or more, 5M or less, 4M or less, 3M or less, 2M or less, 1.5M or less, 1.2M or less, or 1.0M or less. In other aspects, the acid concentration in the etchant 603 can be in the range of about 0.5 M to about 5 M, about 0.5 M to about 4 M, about 0.6 M to about 3 M, about 0.6 M to about 2 M, about 0.8 M to about 1.5 M, about 0.8 M to about 1.2 M, or any range or sub-range therebetween. In other aspects, the etchant 603 can be in contact with the first major surface 109 of the solid electrolyte 108 for a period of time of about 3 minutes or more, about 4 minutes or more, about 5 minutes or more, about 7 minutes or more, about 10 minutes or more, about 20 minutes or less, about 15 minutes or less, about 10 minutes or less, about 8 minutes or less, or about 6 minutes or less. In other aspects, the etchant 603 can be in contact with the first major surface 109 of the solid electrolyte 108 for a time period ranging from about 3 minutes to about 20 minutes, from about 3 minutes to about 15 minutes, from about 4 minutes to about 10 minutes, from about 5 minutes to about 8 minutes, or any range or sub-range therebetween. In other aspects, the temperature at which the etchant 603 is located can be about 15°C or higher, about 20°C or higher, about 22°C or higher, about 25°C or higher, about 40°C or lower, about 30°C or lower, about 27°C or lower, or about 25°C or lower, such as the following range: about 15°C to about 40°C, about 20°C to about 30°C, about 22°C to about 27°C, or any range or sub-range therebetween. In other aspects, etching removes at least a portion of the lithium phase between the garnet crystals (e.g., as described above, the intergranular microstructure extending from the first major surface). As discussed herein, the lithium phase between the garnet crystals of the intergranular microstructure can promote the formation of pores by etching. The pores formed by etching may include features within one or more of the corresponding ranges discussed above (e.g., grain size of about 3 μm or less, 1 μm to 3 μm, or 1 μm to 2 μm; an average pore depth of about 2 μm or greater, about 20 μm to about 60 μm, about 5% or greater of the electrolyte thickness, or about 10% to about 20% of the electrolyte thickness).
[0150] In terms of Figure 7 As shown, the method may include etching the initial second major surface 605 of the solid electrolyte 108 (eg, composite garnet electrolyte) with an etchant 703 (eg, an acid) (see Figure 6 ), thereby forming a composite garnet electrolyte containing pores (e.g., Figure 1-2 In other aspects, as shown, when the second major surface 107 (and / or the initial second major surface 605) of the solid electrolyte 108 is contacted with the etchant 703, the etchant 703 can be contained in the container 701, but the etchant can also be dispensed from the container onto the first major surface (e.g., by spraying). In other aspects, the acid of the etchant 703 can be consistent with the etchant 603 discussed in the previous paragraph and / or fall within one or more ranges or other aspects discussed above for the etchant 603 (e.g., an inorganic acid; a temperature of 15° C. to 40° C. or 20° C. to 30° C.; an acid concentration of 0.5 M to 5 M, 0.5 M to 3 M, or 0.8 M to 1.5 M). In other aspects, the time period that the etchant 603 is in contact with the second major surface 107 (and / or the initial second major surface 605) of the solid electrolyte 108 can be one or more of the corresponding ranges discussed in the previous paragraphs (e.g., about 3 minutes to about 20 minutes or about 4 minutes to about 10 minutes). In other aspects, etching removes at least a portion of the lithium phase between the garnet crystals (e.g., the intergranular microstructure extending from the first major surface as described above). As discussed herein, the lithium phase between the garnet crystals of the intergranular microstructure can promote the formation of pores by etching. The pores formed by etching can include features within one or more of the corresponding ranges discussed above (e.g., a grain size of about 3 μm or less, 1 μm to 3 μm, or 1 μm to 2 μm; an average pore depth of about 2 μm or greater, about 20 μm to about 60 μm, about 5% or greater of the electrolyte thickness, or about 10% to about 20% of the electrolyte thickness). Although Figure 6-7 The first and second major surfaces are shown to be etched in separate steps, but it is to be understood that the entire solid electrolyte may be treated simultaneously, for example by immersing the solid electrolyte in an etchant.
[0151] In terms of Figure 3 and Figure 4 As shown, the method of manufacturing a battery (eg, a solid-state battery) may further include disposing an anode 112 (eg, disposed on a coating 110, see Figure 1). In aspects, arranging the lithium-containing material for the anode 112 may include deposition from the gas phase, such as by sputtering one or more sources (e.g., an elemental target or an alloy target) and / or by thermal evaporation, but other physical vapor deposition (PVD) methods may also be used to form the anode 112. Alternatively, arranging the lithium-containing material for the anode 112 may include arranging the molten material (e.g., lithium metal, lithium alloy) onto the first major surface 109 of the solid electrolyte 108 from, for example, a metal foil, a catheter, a micropipette, or a syringe. Alternatively, the lithium-containing material may be arranged on the solid electrolyte by attaching a metal foil containing the lithium-containing material (e.g., lithium metal, lithium alloy) to the first major surface of the solid electrolyte, which may subsequently be heated to achieve a lithium-containing metal conforming coating surface. In aspects, the lithium-containing metal arranged above the solid electrolyte 108 may be heated in an environment (e.g., an oven) maintained at a first temperature, the first temperature being greater than the melting point of the one or more materials in the lithium-containing material used to form the anode. In other aspects, the first temperature can be about 50°C or more, about 100°C or more, about 125°C or more, or about 150°C or more higher than the melting point of the one or more materials used to form the anode. For example, the melting temperature of lithium metal is about 180°C. In other aspects, the first temperature can be about 280°C or more, about 300°C or more, about 320°C or more, about 500°C or less, about 400°C or less, or about 350°C or less, for example, about 280°C to about 500°C, about 300°C to about 400°C, about 320°C to about 350°C, or any range or sub-range therebetween. In other aspects, the solid electrolyte 108 and the lithium-containing material disposed thereon can be maintained at the first temperature for about 1 minute or more, about 3 minutes or more, about 5 minutes or more, about 15 minutes or more, about 20 minutes or more, about 1 hour or less, about 45 minutes or less, about 30 minutes or less, or about 25 minutes or less, such as the following time range: about 1 minute to about 1 hour, about 3 minutes to about 45 minutes, about 5 minutes to about 30 minutes, about 15 minutes to about 30 minutes, about 20 minutes to about 25 minutes, or any range or sub-range therebetween. Providing a temperature and time within one or more of the ranges described above can achieve the lithium-containing material conforming to the surface on the solid electrolyte 108.
[0152] In terms of Figure 4As shown, the method may also include arranging the intermediate layer 114 by arranging the liquid electrolyte 405 on the cathode 104. In other aspects, the liquid electrolyte may include a lithium salt and a solvent, which may include one or more of the materials discussed above for the intermediate layer 114. In other aspects, the concentration of the lithium salt in the solvent may be within one or more corresponding ranges discussed above. In other aspects, as shown, arranging the liquid electrolyte 405 may include dispensing a predetermined amount of liquid 403 from a container 401 (e.g., a conduit, a hose, a micropipette, or a syringe) to form a liquid electrolyte 405 on the first major surface 105 of the cathode 104. In other aspects, the predetermined amount of the intermediate layer 114 (e.g., liquid electrolyte 405) as the ratio of the volume of the intermediate layer (e.g., liquid electrolyte) to the area of the first major surface of the cathode may be within one or more corresponding ranges discussed above. Providing the ratio of the volume of the intermediate layer to the area of the first major surface of the cathode can minimize the concerns associated with conventional liquid electrolytes (e.g., in liquid-based batteries or hybrid liquid-solid batteries) while being sufficient to wet the interface between the cathode and the solid electrolyte. Although not shown, the cathode may be disposed on the first current collector and the intermediate layer is disposed on the cathode.
[0153] In terms of Figure 5 As shown, the method may further include arranging a solid electrolyte 108 on the cathode 104, as indicated by arrow 501. As shown, the cathode 104 may be opposite to the first major surface 109 of the solid electrolyte 108 and / or the anode 112. As shown, the position of the solid electrolyte 108 is between the cathode 104 and the anode 112, and / or the coating is placed between the cathode 104 and the anode 112. Although not shown, other elements (e.g., current collectors) may be present when the solid electrolyte is arranged on the cathode and / or additional elements may be added after the cathode is arranged to form a battery (e.g., solid-state battery 101 or 201).
[0154] Example
[0155] Various aspects are further illustrated by the following examples. The lithium content of Examples 1-11 and Comparative Examples AA-FF is as described in Table 1. Examples 1-11 differ from Comparative Examples AA-FF only in the amount of excess lithium added when forming the green strip and the firing conditions. Comparative Example CC-FF includes a consolidated granular material of a lithium garnet solid electrolyte having a net thickness of 360 μm and a diameter of 14 mm instead of the sintered strips of Examples 1-11 and Comparative Examples AA-BB. The thickness of Examples 1-11 and Comparative Examples AA-BB is about 80 μm to 160 μm (the table provided below is the specific thickness used for each sample). For the measurements recorded herein, 15 mm diameter discs were laser cut from the material as samples of Examples 1-11 and Comparative Examples AA-BB for the measurements recorded herein (e.g., with a full thickness for the sintered strip). For Tables 2 and 5, the thickness of the sintered strip is 80 μm. For Tables 3-4, the thickness of the sintered strip is 120 μm.
[0156] Lithium garnet solid electrolyte is a cubic phase Li 6.5 Ln3Z 1.4 Ta 0.5 O 12 (LLZTO), which is synthesized from the stoichiometric ratio of Li2CO3(AR), La2O3(99.99%), ZrO2(AR), Ta2O5(99.99%) starting powders. 2 wt% excess Li2CO3 is added to compensate for lithium loss during processing. The raw materials are mixed by dry ball mixing. The powder is calcined at 950°C for 5 hours to form a pure cubic garnet phase powder. For consolidation of granules, granules are formed by hot compacting the garnet powder followed by cutting to the desired size with a wire saw. To shape sintered ribbons, the garnet powder is mixed with an organic binder system comprising a propionate solvent, a dispersant, a plasticizer, an acrylate-based polymer and excess lithium, which is cast using a scalpel to form a green ribbon.
[0157] Table 1: Lithium content of Comparative Examples AA-FF, Examples 1-11, 1A, 4A and 7A
[0158] Example <![CDATA[Final lithium content (wt% Li2O)]]> <![CDATA[Excess Li2O above stoichiometry (wt%)]]> AA-FF 11.1 0 1、1A 11.5 0.4 2 11.5 0.4 3 11.4 0.3 4、4A 11.4 0.3 5 11.3 0.2 6 11.3 0.2 7、7A 11.2 0.1 8 11.3 0.2 9 11.8 0.7 10 11.5 0.4 11 11.3 0.2
[0159] Figure 8803 (Siemens / cm or S / cm). As described above, the lithium content herein refers to the amount in the final electrolyte (determined by flame emission spectroscopy after the electrolyte is fired, not to be confused with the excess lithium added when forming the green ribbon prior to firing). Vertical line 805 is located at 11.1 wt %, which corresponds to the stoichiometric amount of lithium in the garnet crystal. As shown, the maximum ionic conductivity occurs at point 807, which is when the lithium content is stoichiometric (aligned with vertical line 805). The overall distribution of points 809 shows that the ionic conductivity increases sharply above 10 wt % until the stoichiometric amount of lithium is reached, and then the ionic conductivity decreases more gradually as the amount of lithium increases further (see segment 811). Examples 1-11 fall within region 811 (exceeding the stoichiometric lithium amount), with points 813a, 813b, and 813c highlighted representing some compositions within the scope of the present disclosure, with final lithium contents ranging from 11.2 wt% to about 12.2 wt% or 11.3 wt% to about 12.2 wt% Li2O.
[0160] Figure 10-12 SEM images of near-surface cross sections of Comparative Example BB, Comparative Example AA, and Example 3 are shown, respectively (before any etching treatment). Fig.10 As shown, the grain structure of Comparative Example BB is that the grain boundaries 1001 between grains are almost invisible or invisible in the cross section. For Comparative Example AA, Fig.11 The grain structure is also shown as almost invisible or invisible grain boundaries between grains 1101. Fig.10 For Fig.11 With additional visible holes. Fig.12 The near-surface cross section of Example 3 is shown as having main distinct grains (e.g., grains 1203a, 1203b, and 1203c) visible between grain boundaries, indicating that cracks exist between grain boundaries rather than within grains. Comparative Examples AA-BB ( Fig.11 and 10 ) compared to the inter-grain near-surface structure of Example 3 confirms that the additional lithium in Example 3 (relative to the stoichiometric lithium in Comparative Examples AA-BB) produces a change in the microstructure (e.g., morphology) of the garnet electrolyte.
[0161] Figure 13-15 The SEM images of Comparative Example BB, Example 2, and Example 3 are shown, respectively, which were etched in 1M HCl for 20 minutes. Fig.13As shown, the etched surface of Comparative Example BB has visible major grain boundaries; however, there are no visible deep holes. Even after etching in 1M HCl for 20 minutes, it appears that the surface etch is relatively uniform (rather than perhaps better defining the grain boundaries). In contrast, Fig.14 The major surface of Example 2 is shown to be porous with multiple well-defined deep pores, with Example pore 1401 having a pore size 1403 of about 6 μm. Similarly, Fig.15 The major surface of Example 3 is shown to be porous with multiple well-defined deep pores, and the example pores 1501 have a pore diameter 1503 of about 6 μm. Fig.14 (Example 2) and Fig.15 (Example 3), Fig.15 It appears to have more holes, but on average it is Fig.14 The larger pores of Example 2 are associated with the additional lithium (11.5 wt %) compared to Example 3 (11.4 wt %). Overall, the non-porous surface of Comparative Example BB (stoichiometric lithium amount) is significantly different from the large deep pores of both Examples 2-3 (11.4-11.5 wt %). This confirms that Comparative Examples AA-BB ( Fig.11 and 10 ) and Example 3 ( Fig.12 ) is converted into the porous surface ( Figure 14-15 ), which is compared with Comparative Example BB ( Fig.13 It should be understood that Comparative Example BB can still be etched to form a porous surface, but doing so will require more etching (higher acid concentration, higher temperature, longer time, or a combination thereof).
[0162] Figure 16-22 Show complete (or Figure 20-22 An SEM image of a cross-section (from a first major surface 1605, 1705, 1805, 1905, 2005, 2105, or 2205 to a second major surface opposite to the second major surface) of the substrate. Figure 16-22 The samples shown are not etched. Fig.16 Corresponding to Comparative Example BB, Figure 17-22 Corresponding to Examples 2-7 respectively. Fig.16 As shown, the cross section of Comparative Example BB is through the grain through the entire thickness 1603 of the sample. In contrast, Fig.17 The intergranular microstructure throughout the entire thickness 1703 of the sample 1701 of Example 2 is shown, and the intergranular microstructure is mainly in the near-surface region 1707 or 1709. Fig.18The sample 1801 of Example 3 shows the region of inter-grain microstructures 1807 and 1809 near the surface, with the main trans-grain microstructure 1811 therebetween. Fig.18 , the inter-granular microstructure 1807 extends from the first major surface 1805 to a depth 1813 , which appears to be approximately 17% of the thickness 1803 of the sample 1801 . Fig.19 Inter-grain microstructure 1907 is shown near the major surface of sample 1901, with through-grain microstructure 1911 therebetween. Fig. 20 Inter-grain microstructure 2007 is shown to be largely confined within a depth 2103 from the first major surface 2005 of the sample, with through-grain microstructure 2011 further away from the first major surface 2005 . Fig.21 Inter-grain microstructure 2107 is shown extending to at least a depth 2113 from the first major surface 2105 of the sample, with through-grain microstructure 2111 further away from the first major surface 2105. Figure 17-21 , the intragranular microstructure is not predominantly near the first major surface 2205, and appears to be intermixed with the transgranular microstructure in sample 2201 relative to the other samples. Figure 17-22 ) have at least some intergranular microstructure (e.g., near the first major surface), while Comparative Example BB appears to be completely intergranular. In addition, the amount of lithium decreases from 11.5 wt % to 11.2 wt % from Example 2 to Example 7, wherein the decrease in lithium content is associated with a decrease in intergranular microstructure. However, even 11.2 wt % lithium has some intergranular microstructure, which can contribute to the formation of a porous surface by etching compared to a garnet electrolyte with a stoichiometric amount of lithium (11.1 wt %).
[0163] Fig.23 The SEM image of Example 3 is shown after the major surface has been etched with 1M HCl (25°C) for 10 minutes. Fig.23 As shown, sample 2301 includes a porous surface region (e.g., a porous region 2307 extending from first major surface 2305 to a porous depth 2313). As shown, porous region 2307 has a porous depth 2313 of approximately 22 μm, which is approximately 18% of electrolyte thickness 2303. Porous region 2307 includes pores 2311a, 2311b, and 2311c, which may have a width of 5 μm or greater (e.g., 10 μm or greater) and a depth of 10 μm or greater (e.g., 20 μm or greater) extending from the first major surface. Similarly, porous region 2317 includes pores 2321a, 2321b, and 2321c extending from second major surface 2315. Fig.23In the embodiment of the present invention, the depth of the holes (e.g., holes 2311a-c and / or 2321a-c) is approximately the same as the depth associated with the remaining intergranular microstructure. Fig.18 (Example 3 before etching) to Fig.23 (Example 3 after etching), it appears that pores are formed in regions having a large amount of intergranular microstructure.
[0164] Table 2: Firing treatment of Examples 4-7, 4A and 7A
[0165]
[0166] Table 2 presents the firing conditions for Examples 4-7 (as well as 4A and 7A). Examples 4-7 used the same green strip composition, only the firing treatment was changed. As shown in Table 2, increasing the firing temperature from 1100°C to 1160°C caused the amount of lithium content in the resulting composite garnet electrolyte to decrease (even when the time was reduced, see Examples 6-7 vs. Example 5). Combined with the observation that higher amounts of lithium in the resulting composite garnet electrolyte are associated with more intergranular microstructure, this is consistent with lower firing temperatures being associated with more intergranular microstructure.
[0167] Table 3 also presents the firing conditions for Examples 9-11. Examples 9-11 used the same green ribbon composition (with more excess lithium than that of Examples 4-7), only the firing treatment was changed. Similar to the trend seen for Examples 4-7, increasing the firing temperature from 1125°C to 1185°C (Examples 9-11) was associated with a decrease in the amount of lithium content in the resulting composite garnet electrolyte. This is consistent with the trends noted above and supports the view that lower firing temperatures are associated with more intergranular microstructure.
[0168] Table 3 also presents the ring-on-ring strength of Examples 9-11. As shown, Example 10 has a ring-on-ring strength of about 340 MPa. Based on the final lithium content (similar to Fig.17 Example 2 shown), Example 10 is expected to have intergranular microstructure primarily in the near-surface region. In addition, based on the trend of more intergranular microstructure at lower firing temperatures, it appears that an appropriate amount of intergranular microstructure can increase the strength of the composite garnet electrolyte (e.g., the maximum strength is about 11.5 wt% Li2O).
[0169] Table 3: Firing treatment of Examples 9-11
[0170]
[0171] Figure 24-25SEM images of the surfaces of Examples 4 and 7 after etching with 1 M HCl (25° C.) for 10 minutes are presented, respectively. Figure 24-25 The lower zoom factor makes Figure 24-25 The images in Figure 14-15 So clear, but Figure 24-25 The pore structure can still be seen in Fig.24 In FIG. 2 , holes (e.g., holes 2401 ) are seen passing through the surface, such as holes 2401 having a pore size 2403 of about 6 μm. Fig.25 In the example, grains 2051 on the surface are visible, as well as holes (eg, holes 2505), such as holes 2505 having a hole diameter 2503 of about 3 μm. Fig.24 ) compared to Example 7 ( Fig.25 )The larger pore size is consistent with the trend discussed above: more lithium (11.4 wt % for Example 4 and 11.2 wt % for Example 7) leads to more intergranular microstructure and thus easier etching and larger pores.
[0172] Fig.26 The pore size distributions of Examples 12-13 and Comparative Examples CC-DD etched with 3M HCl (25°C) for 10 minutes are presented. Fig.26 , the horizontal axis 2601 corresponds to the pore size (in μm) and the vertical axis 2607 corresponds to the differential indentation in the mercury porosity measurement (mL / g). Curves 2605 and 2607 correspond to Examples 12-13, which are sintered ribbons with 11.2 wt% and 11.4 wt% lithium amounts, respectively. Curves Comparative Examples CC-DD correspond to hot compacted samples with stoichiometric (11.1 wt%) lithium. It is believed that the large peaks of curves 2611 and 2613 above 10 μm (on the left) correspond to the inter-crack volume of the sample (due to the hot compaction method) rather than surface pores. Ignoring the peak from the inter-crack volume, Comparative Example CC has a median pore size of about 3 μm (curve 2611), while Comparative Example DD has a median pore size of about 7 μm (curve 2613). In contrast, Examples 12-13 (curves 2605 and 2607) have a relatively small peak at about 7 μm in addition to a larger peak corresponding to pores greater than 10 μm. This is consistent with all of the larger pores seen associated with composite garnet electrolytes having excess stoichiometric amounts of lithium.
[0173] NCM523 refers to LiNi 0.5 Co 0.2 Mn 0.3O2 (commercially available precursor from Landt Instruments). NCM523 precursor, Super P carbon black (purchased from Timcal-Imerys) and poly (vinylidene fluoride) (PVDF) (dissolved in N-methylpyrrolidone) were formed into a slurry in a weight ratio of 8:1:1, which was coated on an aluminum (Al) foil at a predetermined thickness and dried in vacuum. After etching the surface of the solid electrolyte in 1M HCl for 10 minutes, the lithium-containing material for the anode was arranged on the coating and heated at 300°C for 5 minutes. The cathode had 20 mg / cm 2 The mass loading of the NCM 523 cathode is 12 mm in diameter. In Examples 1, 1A and 8 and Comparative Example AA, 16 μL / cm 2 A liquid electrolyte consisting of 1M LIFSI dissolved in sulfolane was placed on the cathode, and then a solid electrolyte was placed above the cathode with the liquid electrolyte placed in between. In Examples 4 and 4A and Comparative Example BB, 16 μL / cm 2 A liquid electrolyte consisting of 3M LIFSI dissolved in sulfolane was placed on the cathode, and then a solid electrolyte was placed above the cathode with the liquid electrolyte placed in between. Examples 1, 1A, 4 and 4A and Comparative Examples AA-BB were formed into batteries, such as CR2025 button cell format. Figure 2 The solid-state battery 201 shown has Ni foam arranged above the anode.
[0174] Fig. 9 Nyquist plots for Example 1A and Comparative Example AA are shown. Example 1A has the same composition as Example 1, but Example 1A was etched in 1M HCl for 5 minutes instead of 20 minutes for Example 1. Comparative Example AA was also etched in 1M HCl for 5 minutes. For both Example 1A and Comparative Example AA, both major surfaces (the one facing the cathode and the one facing the anode) were etched in 1M HCl for 5 minutes. From anode to cathode, the cell configurations for the EIS tests for Example 1A and Comparative Example AA were: Li 0.9 Mg 0.1 Alloy anode, composite garnet electrolyte of Example 1A or Comparative Example AA, 16 μL / cm 2 A liquid electrolyte consisting of 1M LiFSI in 1M sulfolane (based on the surface area of the cathode), and an NCM523 cathode. As discussed above, the impedance was measured by EIS using a Solartron 1260A (Solartron) impedance analyzer at 25°C for frequencies from 0.1 Hz to 1 megahertz (MHz). Fig. 9 The data shown. Fig. 9 In the example, the horizontal axis 901 corresponds to the real part of the impedance (Z', measured in Ωcm 2), while the vertical axis 903 corresponds to the imaginary part of the impedance (Z), measured in Ωcm 2 ). The interface resistance shown in Table 2 is measured as the difference between the real parts of the impedance at the end points of the arcs of the curves corresponding to the EIS results in the Nyquist plot. Curve 905 corresponds to Comparative Example AA, while curve 907 corresponds to Example 1A. As shown, for the combined arc, the interface resistance of Comparative Example AA (curve 907) is more than twice that of Example 1A (curve 905) (e.g., Comparative Example AA is about 35 Ω cm 2 , in contrast, Example 1A is about 12Ωcm 2 ). The overall arcs of the two curves 905 and 907 appear to have: a lower frequency arc (on the left), which can be attributed to the cathode-garnet interface, and a higher frequency arc (on the right), which can be attributed to the anode-garnet interface. For both of these interfaces (as part of the overall arc), the distance along the horizontal axis 901 is less for Example 1A (curve 907) than for Comparative Example AA (curve 905). This confirms that the additional lithium of Example 1 enables the formation of a porous surface with a lower interface resistance than Comparative Example AA.
[0175] Table 4 presents the cell performance of Examples 4 and 8 of the button cell form factor, and Table 5 presents the cell performance of Examples 4-7 of the soft pack cell form factor. The half-cell used to determine the "half-cell CCD" includes lithium alloy electrodes on both surfaces of an acid-etched composite garnet electrolyte with a porous surface. As shown in Table 2, Example 4 (with more lithium than Example 8) has a higher critical current density (CCD) than Example 8. The cells described above were subjected to complete cell cycle stability. The complete cell tests of Examples 4 and 8 are as follows: at 1 mA / cm 2 , 1.5mA / cm 2 or 2mA / cm 2 The constant charge and discharge current density of either of the two cycles was up to 3.2 mAh / cm 2 The nominal capacity of Example 8 lasted for 70 cycles. As shown in Table 4, Example 8 had a nominal capacity of 1 mA / cm before failure. 2 The current density withstood 28 cycles, and for 1.5 mA / cm 2 In contrast, for all current densities tested (up to 2 mA / cm2 reported in Table 4), 2 ), Example 4 all withstood a full 70 cycles.
[0176] Table 4: Cell performance of Examples 4 and 8
[0177]
[0178] Table 5: Cell performance of Examples 4-7
[0179]
[0180]
[0181] For Table 5, the composite garnet electrolytes with porous surfaces of Examples 4-7 were assembled into soft pack cells. For the soft pack cells, a 300 nm gold layer was sputtered onto the first major surface of the acid-etched composite garnet electrolyte with a porous surface, followed by pressing a 0 μm Li foil (250 MPa cool pressing followed by 80°C heat treatment for 1 hour) to form an anode. The NCM523 cathode was arranged on the second major surface of the composite garnet electrolyte with a porous surface, with a 16 μL / cm 2 1MLiFSI.
[0182] For the "C / 8 Discharge Test", the discharge rate was maintained at C / 8, while the charge rate was increased in the following manner (3 cycles at each rate): C / 12, C / 8, C / 3, C / 2, and C / 1. As shown in Table 5, for Example 7, 0% of the cells tested successfully passed all cycles without failure, but the proportion of cells that survived increased from Example 7 to Example 4. For Example 6, 40% of the cells survived all tests; for Example 5, 50% of the cells survived all tests; and for Example 4, 80% of the cells survived all tests.
[0183] For the "C / 6 Discharge Test", the discharge rate was maintained at C / 6, while the charge rate was increased in the following manner (3 cycles at each rate): C / 12, C / 8, C / 3, C / 2, and C / 1, which is the same charge rate ramp as the C / 8 test above. For the C / 6 test, for Example 7, 0% of the cells tested successfully passed all cycles without failure, but the percentage of cells that survived increased from Example 7 to Example 4. For Example 6, 20% of the cells survived all tests; for Example 5, 25% of the cells survived all tests; and for Example 4, 40% of the cells survived all tests. The charge ramp test results confirm that an increase in the amount of lithium (e.g., from 11.2 wt % to 11.3 wt % or from 11.2 wt % to 11.4 wt %) improves the cycling stability, even at least the C / 1 charge rate.
[0184] Table 5 also presents the number of cycles that Examples 4 and 7 withstood without failure (Examples 5 and 6 were not tested). 2The samples were cycled at a nominal capacity of 100 cycles for a maximum of 100 cycles. As shown in Table 5, Example 7 failed before completing one cycle, while Example 4 withstood all test cycles.
[0185] The above observations can be combined to provide solid electrolytes, batteries and methods of making the same, wherein the surface (or surfaces) of the solid electrolytes included can be easily etched to form electrolytes having porous surfaces (e.g., composite garnet electrolytes having porous surfaces). Electrolytes having porous surfaces (e.g., composite garnet electrolytes having porous surfaces) can achieve lower interfacial resistance, increased charging performance and / or increased cycle stability. In addition, electrolytes having porous surfaces (e.g., composite garnet electrolytes having porous surfaces) can achieve high ring-on-ring strength (e.g., about 150 MPa or more or about 150 MPa to about 400 MPa).
[0186] As described herein, providing an excess of lithium in the composite garnet electrolyte (0.1 wt % to 4 wt %, 0.2 wt % to 1.1 wt %, or 0.3 wt % to 0.9 wt %) can help form a mixture of intergranular and transgranular microstructures and help etch a solid electrolyte (e.g., a composite garnet electrolyte) to form a solid electrolyte with a porous surface (e.g., a composite garnet electrolyte with a porous surface). For example, providing 11.2 wt % to 15 wt % or 11.3 wt % to 12.2 wt % can form an intergranular microstructure near a major surface of the composite garnet electrolyte, which can help etch the composite garnet electrolyte to form a solid electrolyte with a porous surface. Providing a transgranular microstructure near and / or at the first major surface can help form large and / or deep pores therein.
[0187] As described herein, the amount of lithium is determined based on flame emission spectroscopy, which means that the amount of lithium refers to the actual amount of lithium in the resulting solid electrolyte (e.g., composite garnet electrolyte). This is different from the amount of lithium that can be added to the garnet crystals before firing (e.g., sintering) to form the solid electrolyte, because it is known that lithium volatilizes during the firing process. As described in the examples below, adjusting the firing conditions themselves will change the amount of lithium present in the resulting solid electrolyte.
[0188] The green strip may contain excess lithium (e.g., 0.5 wt % or more, 2 wt % or more, or 10 wt % or more, based on the amount of garnet in the green strip) that is not completely removed by firing (e.g., sintering). The combination of firing conditions and excess lithium determines the amount of lithium that remains in the resulting electrolyte. If the firing temperature is too high (e.g., greater than 1200° C.) and / or the duration is too long (e.g., about greater than 60 minutes, depending on the temperature), the vast majority of the excess lithium added to the green strip may volatilize to produce an electrolyte that does not have a transgranular microstructure unlike aspects of the present disclosure.
[0189] Without wishing to be bound by theory, it is believed that the lithium phase between the garnet grains of the composite garnet electrolyte in the region having the intergranular microstructure may be preferentially etched, and thus the composite garnet electrolyte of the present disclosure may be more easily and / or more rapidly etched than other garnet electrolytes (e.g., having a stoichiometric amount of lithium). Providing a grain size of about 3 μm or less, about 1 μm to about 3 μm, or 1 μm to 3 μm may enable increased ionic conductivity, for example by reducing the path length along the grain boundaries along which ions transported through the solid electrolyte sheet move and / or by providing additional grain boundaries per unit volume of the solid electrolyte. Providing deep pores (e.g., about 2 μm or greater, about 20 μm to about 60 μm, about 5% of the electrolyte thickness or greater, or about 10% to about 20% of the electrolyte thickness) can increase the effective surface area of the solid electrolyte (e.g., facing the anode and / or facing the cathode), which can reduce the interfacial resistance of a battery comprising a solid electrolyte having a porous surface (e.g., a composite garnet electrolyte having a porous surface).
[0190] Directional terms used herein, such as up, down, left, right, front, back, top, and bottom, are only used with reference to the drawings and are not intended to represent absolute orientations.
[0191] It will be understood that the various aspects disclosed may relate to specific features, elements or steps described with a particular aspect. It will also be understood that although specific features, elements or steps are described in conjunction with one aspect, different aspects may be interchanged or combined with each other in various combinations or permutations not shown.
[0192] It is also to be understood that the terms "the," "an," or "an" as used herein mean "at least one" and should not be limited to "only one" unless expressly specified to the contrary. Thus, for example, reference to "an" component includes aspects having two or more such components unless the context clearly indicates otherwise. Similarly, "plurality" is intended to mean "more than one."
[0193] As used herein, the term "about" indicates that the amount, size, formulation, parameter and other variables and characteristics are not and need not be exact, but may be approximate and / or larger or smaller as needed, reflecting tolerances, conversion factors, rounding and measurement errors, etc., as well as other factors known to those skilled in the art. Herein, a range may be expressed as starting from "about" another specific value and / or terminating at "about" another specific value. When such a range is expressed, aspects include starting from a specific value and / or ending at another specific value. Similarly, when the antecedent "about" is used to indicate that a numerical value is an approximate value, it should be understood that a specific numerical value constitutes another aspect. Regardless of whether the numerical value or the endpoint of a range of this specification is stated as "about", the numerical value or the endpoint of the range is intended to include two aspects: one modified by "about" and one not modified by "about". It should also be understood that the endpoint values of each range are meaningful when they are related to another endpoint value and when they are not related to another endpoint value.
[0194] As used herein, the terms "substantially," "substantially," and variations thereof are intended to mean that the described feature is equal to or approximately the same as a value or description. For example, a "substantially flat" surface is intended to mean a flat or approximately flat surface. Additionally, as defined above, "substantially similar" is intended to mean that two values are equal or approximately equal. In aspects, "substantially similar" can mean that the values are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.
[0195] Unless otherwise stated, it is not intended that any method described herein be construed as requiring that its steps be performed in a specific order. Therefore, when a method claim does not actually state that its steps follow a certain order or it does not specifically indicate in any other way in the claims or description that the steps are limited to a specific order, it is not intended to imply any particular order.
[0196] Although the transitional term "comprising" may be used to disclose various features, elements, or steps of a particular aspect, it is to be understood that this implies including alternative aspects that may be described using the transitional terms "consisting of," "consisting essentially of." Thus, for example, implicit alternative aspects for a device comprising A+B+C include aspects where the device consists of A+B+C and aspects where the device consists essentially of A+B+C. As used herein, unless otherwise noted, the terms "comprising" and "including" and variations thereof should be understood to be synonymous and open ended.
[0197] The above-described aspects and features of those aspects are exemplary and may be provided alone or in any combination with any one or more features of the other aspects provided herein without departing from the scope of the present disclosure.
[0198] It is obvious to those skilled in the art that various modifications and changes can be made to the present disclosure without departing from the scope and spirit of the present disclosure. Therefore, the present disclosure covers modifications and changes to aspects of this document as long as they fall within the scope of the appended claims and their equivalents.
Claims
1. A method for manufacturing a porous surface of a composite garnet electrolyte, comprising: etching at least a first major surface of the composite garnet electrolyte with an acid to form a porous surface of the composite garnet electrolyte comprising pores, The composite garnet electrolyte comprises: an intergranular microstructure extending from a first major surface to a first depth, the composite garnet electrolyte comprising a lithium phase between garnet crystals, and an electrolyte thickness defined between the first major surface and a second major surface opposite to the first major surface.
2. The method of claim 1, wherein: The etching removes at least a portion of the lithium phase.
3. The method according to any one of claims 1 to 2, wherein: The amount of lithium in the composite garnet electrolyte is about 11.2 wt % to about 15 wt % based on the oxide of the composite garnet electrolyte.
4. The method of claim 3, wherein: The amount of lithium in the composite garnet electrolyte is about 11.3 wt % to about 12.2 wt %.
5. The method according to any one of claims 1 to 2, wherein: The amount of lithium in the composite garnet electrolyte is about 0.1 wt % to about 4 wt % greater than the stoichiometric lithium amount of the garnet crystals, based on the oxide of the composite garnet electrolyte.
6. The method of claim 5, wherein: The amount of lithium in the composite garnet electrolyte exceeds the stoichiometric amount of lithium by about 0.2 wt % to about 1.1 wt %.
7. The method according to any one of claims 1 to 6, wherein: The intergranular microstructure extends from the first major surface to a first depth that is approximately 10% or more of the thickness of the electrolyte.
8. The method of claim 7, wherein: The composite garnet electrolyte comprises a transgranular microstructure located between regions comprising an intergranular microstructure.
9. The method according to any one of claims 1 to 8, wherein: The median grain size of garnet crystals is less than 3 μm.
10. The method according to any one of claims 1 to 9, wherein: The median pore diameter of the pores is greater than 0.25 μm.
11. The method of claim 10, wherein: The median pore size of the pores is 3 μm to about 20 μm.
12. The method of any one of claims 1 to 11, further comprising: Prior to etching, contacting the first major surface with water for at least 1 minute, The acid concentration during the etching process is about 0.5M to about 5M.
13. The method of any one of claims 1 to 12, further comprising: casting a green ribbon comprising garnet, excess lithium, a binder, and a solvent, wherein the amount of excess lithium is greater than 5 wt % based on the weight % of the amount of garnet; and The green strips are fired to form the composite garnet electrolyte.
14. The method of claim 13, wherein: Firing includes heating the green strip at a temperature of about 900°C to about 1150°C for a period of 60 minutes or less.
15. The method according to any one of claims 1 to 14, wherein: The composite garnet electrolyte comprises a ring-on-ring strength of about 150 MPa to about 600 MPa.
16. The method according to any one of claims 1 to 15, wherein: The interfacial resistance of the composite garnet electrolyte with a porous surface at 25° C. is less than or equal to 20Ω.
17. A composite garnet electrolyte comprising: a hole extending from the first major surface; as well as an intergranular microstructure extending from the first major surface to a first depth, The composite garnet electrolyte includes: a lithium phase between garnet crystals, and an electrolyte thickness defined between a first major surface and a second major surface opposite to the first major surface.
18. The composite garnet electrolyte according to claim 17, wherein The amount of lithium in the composite garnet electrolyte is about 11.2 wt % to about 15 wt % based on the oxide of the composite garnet electrolyte.
19. The composite garnet electrolyte according to claim 18, wherein The amount of lithium in the composite garnet electrolyte is about 11.3 wt % to about 12.2 wt %.
20. The composite garnet electrolyte according to claim 17, wherein The amount of lithium in the composite garnet electrolyte is about 0.1 wt % to about 4 wt % greater than the stoichiometric lithium amount of the garnet crystals, based on the oxide of the composite garnet electrolyte.
21. The composite garnet electrolyte according to claim 20, wherein The amount of lithium in the composite garnet electrolyte is about 0.2 wt % to about 1.1 wt % more than the stoichiometric lithium amount of the garnet crystal.
22. The garnet electrolyte according to any one of claims 18 to 21, wherein The intergranular microstructure extends from the first major surface to a first depth that is approximately 10% or more of the thickness of the electrolyte.
23. The garnet electrolyte of claim 22, wherein The garnet electrolyte comprises a transgranular microstructure located between regions comprising an intergranular microstructure.
24. The porous garnet electrolyte according to any one of claims 18 to 23, wherein The median grain size of garnet crystals is less than 3 μm.
25. The porous garnet electrolyte according to any one of claims 18 to 24, wherein The median pore diameter of the pores is greater than 0.25 μm.
26. The porous garnet electrolyte according to any one of claims 18 to 25, wherein The porous garnet electrolyte comprises a ring-on-ring strength of about 150 MPa to about 600 MPa.
27. The garnet electrolyte of any one of claims 26 to 39, wherein The interfacial resistance of the garnet electrolyte at 25°C is less than or equal to 20Ω.
28. A battery comprising: A lithium-containing anode; The garnet electrolyte according to any one of claims 26 to 39; as well as cathode, The garnet electrolyte is located between the lithium-containing anode and the cathode.
29. The battery of claim 28, wherein The battery can withstand 2mA / cm at 60℃ 2 or higher critical current density.
30. The battery of any one of claims 28-29, wherein The battery can withstand 70 cycles of 2mA / cm 2 of charge and discharge cycles.
Citation Information
Cited By
Composite garnet electrolytes with a porous surface, batteries, and methods of making the same
WO2025096192A1